Electrode composition, electrode sheet for all-solid-state secondary battery, and all-solid-state secondary battery, and manufacturing method of the latter two
Patent Information
- Application Number
- CN202280039951.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-07
- Filing Date
- 2022-07-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-07-07
AI Technical Summary
但是,作为形成全固态二次电池的活性物质层的材料(活性物质层形成材料),对于含有上述无机固体电解质、活性物质及导电助剂等的材料(电极组合物),在专利文献1及专利文献2中没有研究
[0042]本发明能够提供一种即使提高固体成分浓度也具有优异的分散稳定性的电极组合物,其通过用作全固态二次电池的活性物质层形成材料,能够实现抑制电池电阻的上升和优异的循环特性。并且,本发明能够提供一种具有由该电极组合物构成的活性物质层的全固态二次电池用电极片及全固态二次电池。此外,本发明能够提供一种使用该电极组合物的全固态二次电池用电极片及全固态二次电池的制造方法。
Smart Images

Figure CN117425973B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an electrode composition, an electrode sheet for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method for manufacturing the electrode sheet for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Technology
[0002] A secondary battery is a rechargeable battery that has a negative electrode, a positive electrode, and an electrolyte sandwiched between the negative and positive electrodes, and can be charged and discharged by causing specific metal ions such as lithium ions to move back and forth between the two electrodes.
[0003] Non-aqueous electrolyte secondary batteries using organic electrolytes are widely used for various applications, but research is underway on electrodes and their forming materials to further improve battery performance, such as rate characteristics. For example, Patent Document 1 describes a slurry containing an electrode active material, a conductive material, and a dispersant composed of an ionic surfactant. It describes how, in this slurry, the conductive material uniformly coats the surface of the electrode active material using the dispersant composed of an ionic surfactant. Furthermore, Patent Document 2 describes a solution for forming a coating of a positive electrode active material, which is a solution in which a conductive agent is further mixed into a coating polymer compound solution containing positive electrode active material powder, a coating polymer compound, and isopropanol.
[0004] However, non-aqueous electrolyte secondary batteries using organic electrolytes are prone to liquid leakage and are susceptible to internal short circuits due to overcharging or over-discharging, thus requiring further improvements in safety and reliability.
[0005] In this context, all-solid-state secondary batteries that use inorganic solid electrolytes instead of organic electrolytes have attracted attention. The negative electrode, electrolyte, and positive electrode of this all-solid-state secondary battery are all made of solids, which can significantly improve the safety and reliability of batteries using organic electrolytes. It can also extend battery life. Furthermore, all-solid-state secondary batteries can be configured with electrodes and electrolytes directly arranged and connected in series. Therefore, compared to non-aqueous electrolyte secondary batteries using organic electrolytes, they can achieve higher energy density and are expected to be used in electric vehicles or large-scale storage batteries.
[0006] Regarding the constituent layers of secondary batteries, whether they are non-aqueous electrolyte secondary batteries or all-solid-state secondary batteries, as described in Patent Documents 1 and 2, a slurry composition obtained by dispersing or dissolving the materials forming the constituent layers in a dispersion medium is typically used to form the membrane.
[0007] However, in recent years, inorganic solid electrolytes, especially oxide-based and sulfide-based inorganic solid electrolytes, have attracted much attention as materials forming the constituent layers (active material layer, solid electrolyte layer, etc.) of all-solid-state secondary batteries, due to their high ionic conductivity approaching that of organic electrolytes. Research and development of all-solid-state secondary batteries utilizing the properties of these inorganic solid electrolytes are progressing rapidly. However, as for the active material layer forming material (active material layer forming material), materials containing the aforementioned inorganic solid electrolyte, active material, and conductive additives (electrode composition) have not been studied in Patent Documents 1 and 2.
[0008] Previous technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2018-073687
[0011] Patent Document 2: Japanese Patent Application Publication No. 2017-188455 Summary of the Invention
[0012] The technical problem to be solved by the invention
[0013] Because the constituent layers of an all-solid-state secondary battery are formed by solid particles (inorganic solid electrolyte, active material, conductive additives, etc.), the interfacial contact states between solid particles and between solid particles and current collectors are limited, making it easy for the interfacial resistance to increase. This increase in interfacial resistance not only leads to an increase in the overall resistance of the all-solid-state secondary battery (reduced ionic conductivity) but also a decrease in the cycle characteristics of the all-solid-state secondary battery.
[0014] The increase in resistance, which is the main cause of battery performance degradation, is not only due to the interfacial contact state of solid particles, but also primarily due to the uneven presence (configuration) of solid particles within the constituent layer. Therefore, when forming the constituent layer with a constituent layer forming material, it is required that the material stably maintain the dispersion characteristics of the freshly prepared solid particles (dispersion stability).
[0015] Furthermore, in recent years, from the perspective of reducing environmental impact and thus manufacturing costs, high-concentration compositions (slurries) with increased solids content have been studied as constituent layer forming materials. However, as the solids content of the composition increases, the properties of the composition usually deteriorate significantly. The same applies to dispersion stability, etc.; in high-concentration compositions, it is difficult to achieve the required dispersion stability.
[0016] The objective of this invention is to provide an electrode composition that exhibits excellent dispersion stability even with increased solid component concentration, which, when used as an active material layer forming material in an all-solid-state secondary battery, enables suppression of battery resistance increases and excellent cycle characteristics. Furthermore, the objective of this invention is to provide an electrode sheet for an all-solid-state secondary battery using this electrode composition, an all-solid-state secondary battery, and a method for manufacturing the electrode sheet for an all-solid-state secondary battery and an all-solid-state secondary battery.
[0017] means for solving technical problems
[0018] Based on in-depth research into electrode compositions, the inventors arrived at the following concept: For inorganic solid electrolytes, improvements in dispersion stability can be expected to some extent through modifications to polymer binders, etc. However, in electrode compositions where conductive additives with poor dispersibility relative to the dispersion medium coexist, comprehensively improving the behavior of the polymer binder relative to the conductive additives in the dispersion medium helps to improve dispersion stability. Based on this idea, the inventors conducted further research and discovered that the polymer binder used in combination with solid particles is formed from polymers with specific molecular weights. By imparting properties that dissolve in the dispersion medium, it exhibits appropriate affinity and disperses the conductive additives as particles of a specific size in the dispersion medium. Even with increased solid component concentration, excellent dispersion stability of the electrode composition can be maintained. Furthermore, it was found that by using this electrode composition as an active material layer forming material, an all-solid-state secondary battery capable of suppressing the rise in battery resistance and exhibiting excellent cycle characteristics can be manufactured.
[0019] Based on these insights, the present invention underwent further and repeated research, thereby completing the present invention.
[0020] That is, the above-mentioned problems are solved through the following solutions.
[0021] <1> An electrode composition comprising an inorganic solid electrolyte (SE) having conductivity of ions belonging to Group 1 or Group 2 of the periodic table, an active material (AC), a conductive additive (CA), a polymer binder (B), and a dispersion medium (D), and satisfying the following conditions (1) to (4),
[0022] (1) The polymer binder (B) is dissolved in the dispersion medium (D).
[0023] (2) Adsorption rate of the polymer binder (B) on the conductive additive (CA) in the dispersion medium (D) [A] CA [Above 0% and below 50%]
[0024] (3) The polymer constituting the polymer adhesive (B) has a mass-average molecular weight of 6,000 or more.
[0025] (4) Conductive additives present in the active material layer formed by the electrode composition.
[0026] The average particle size of (CA) is less than 1.0 μm.
[0027] <2> According to the electrode composition described in <1>, wherein the adsorption rate [A] CA The percentage is between 5% and 30%.
[0028] <3> According to the electrode composition described in <1> or <2>, wherein the adsorption rate of the polymer binder (B) on the inorganic solid electrolyte (SE) in the dispersion medium (D) [A] SE The percentage is below 45%.
[0029] <4> The electrode composition according to any one of <1> to <3>, wherein the mass-average molecular weight is 10,000 to 700,000.
[0030] <5> The electrode composition according to any one of <1> to <4>, wherein the difference ΔSP between the SP value of the dispersion medium (D) and the SP value of the polymer constituting the polymer binder (B) is 3.0 MPa. 1 / 2 the following.
[0031] <6> The electrode composition according to any one of <1> to <5>, wherein the polymer forming the polymer binder (B) comprises a constituent having a functional group selected from the functional group (a) below,
[0032] <Functional Groups (a)>
[0033] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, ether bond, imino, ester bond, amide bond, carbamate bond, urea bond, heterocyclic group, aryl, carboxylic anhydride group.
[0034] <7> The electrode composition according to any one of <1> to <6>, wherein the inorganic solid electrolyte (SE) is a sulfide-based inorganic solid electrolyte.
[0035] <8> An electrode sheet for an all-solid-state secondary battery, having an active material layer composed of any one of the electrode compositions described in <1> to <7> above.
[0036] <9> According to <8>, the electrode sheet for all-solid-state secondary batteries has an average particle size of less than 0.5 μm for the conductive additive (CA) in the active material layer.
[0037] <10> The electrode sheet for all-solid-state secondary batteries according to <8> or <9>, wherein the electronic conductivity of the active material layer is 30 mS / cm or higher.
[0038] <11> An all-solid-state secondary battery, comprising a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence, wherein at least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer composed of an electrode composition as described in any one of <1> to <7>.
[0039] <12> A method for manufacturing an electrode sheet for an all-solid-state secondary battery, wherein the electrode composition described in any one of <1> to <7> is used to form a film.
[0040] <13> A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is manufactured by the manufacturing method described in <12> above.
[0041] Invention Effects
[0042] This invention provides an electrode composition that exhibits excellent dispersion stability even with increased solid component concentration. By being used as an active material layer forming material in an all-solid-state secondary battery, it enables suppression of battery resistance increases and excellent cycle characteristics. Furthermore, this invention provides an electrode sheet for an all-solid-state secondary battery having an active material layer composed of this electrode composition, and an all-solid-state secondary battery. Additionally, this invention provides a method for manufacturing an electrode sheet for an all-solid-state secondary battery using this electrode composition and an all-solid-state secondary battery.
[0043] The above-described features and other features and advantages of the present invention will become more apparent from the accompanying drawings and from the following description. Attached Figure Description
[0044] Figure 1 This is a longitudinal sectional view illustrating a preferred embodiment of the all-solid-state secondary battery of the present invention. Detailed Implementation
[0045] In this invention, the numerical range indicated by "~" refers to the range encompassed by the values recorded before and after "~" as the lower and upper limits. Furthermore, in this invention, when multiple numerical ranges are defined for the content, physical properties, etc., of a component, the upper and lower limits forming the numerical range are not limited to a specific combination recorded before and after "~" as a specific numerical range; rather, they can be defined as a numerical range formed by appropriately combining the upper and lower limits of each numerical range.
[0046] In this invention, the designation of a compound (e.g., when referred to as a compound by appending a compound at the end) means that in addition to the compound itself, it also includes its salt and its ions. Furthermore, it refers to derivatives that include modifications to the introduced substituents or other components without impairing the effects of this invention.
[0047] In this invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylates.
[0048] In this invention, the term "substituent, linking group, etc." (hereinafter referred to as "substituent, etc.") that is not explicitly stated as substituted or unsubstituted means that the group may also have suitable substituents. Therefore, in this invention, even when simply stated as a YYY group, the YYY group includes not only those without substituents but also those with substituents. This also applies to compounds where substitution or unsubstituent is not explicitly stated. As a preferred substituent, substituent Z, described later, can be cited as an example.
[0049] In this invention, when multiple substituents, etc., are represented by specific symbols, or when multiple substituents, etc., are specified simultaneously or selectively, it means that each substituent, etc., may be the same as or different from each other. Furthermore, even without special explanation, when multiple substituents, etc., are adjacent, it means that they may be linked together or fused together to form a ring.
[0050] In this invention, "polymer" refers to a polymer, synonymous with "high molecular weight compound." Furthermore, "polymer adhesive" (also simply "adhesive") refers to an adhesive composed of polymers, including the polymer itself and adhesives formed by containing polymers.
[0051] In this invention, a composition containing an inorganic solid electrolyte, an active material, a conductive additive, and a polymer binder, and used as a material for forming the active material layer of an all-solid-state secondary battery (active material layer forming material) is called an electrode composition (also called an electrode composition for an all-solid-state secondary battery). On the other hand, a composition containing an inorganic solid electrolyte, a suitable polymer binder, and used as a material for forming the solid electrolyte layer of an all-solid-state secondary battery is called an inorganic solid electrolyte-containing composition, which typically does not contain an active material or a conductive additive.
[0052] In this invention, the electrode composition comprises a positive electrode composition containing a positive electrode active material and a negative electrode composition containing a negative electrode active material. Therefore, sometimes either or both of the positive electrode composition and the negative electrode composition are simply referred to as the electrode composition, and sometimes either or both of the positive electrode active material layer and the negative electrode active material layer are simply referred to as the active material layer or the electrode active material layer. Furthermore, either or both of the positive electrode active material and the negative electrode active material are collectively referred to simply as the active material or the electrode active material.
[0053] [Electrode Composition]
[0054] The electrode composition of the present invention contains an inorganic solid electrolyte (SE) with conductivity of ions belonging to Group 1 or Group 2 of the periodic table, an active material (AC), a conductive additive (CA), a polymer binder (B), and a dispersion medium (D), and satisfies conditions (1) to (4) described later. Even with an increase in the concentration of the solid component, the electrode composition can stably maintain excellent stability after adjustment over time (excellent dispersion stability). By using the electrode composition as an active material layer forming material, an active material layer satisfying the properties described later can be formed, enabling the realization of an all-solid-state secondary battery exhibiting suppression of battery resistance rise and excellent cycle characteristics.
[0055] The detailed reasons are still unclear, but the following is believed.
[0056] The polymer binder (B) is composed of polymers with high molecular weights within a specific range (condition (3)) and dissolved in the dispersion medium (D) (condition (1)). Therefore, the molecular chains of the polymer binder (B) are extensively extended in the dispersion medium (D). By making such a polymer binder (B) exhibit appropriate adsorption (affinity) for the conductive additive (CA) (condition (2)), the polymer binder suppresses excessive adsorption of solid particles, especially the conductive additive (CA), in the dispersion medium (D) and during the film formation process of the electrode composition. At the same time, it effectively suppresses the adsorbed solid particles from repelling each other (re)aggregating or precipitating, and enables the conductive additive (CA) to exist as particles with an average particle size of less than 1 μm (condition (4)). Moreover, during the film formation process of the electrode composition, the solid particles in the active material layer can directly contact each other, and the conduction pathways (electronic conduction pathways and ionic conduction pathways) containing the conductive additive (CA) can be fully constructed. Therefore, the interfacial resistance between solid particles and the increase in the resistance of the active material layer can be suppressed.
[0057] When this electrode composition with excellent dispersion stability is used to form the active material layer, it is possible to suppress uneven distribution of solid particles and aggregation of conductive additives (CA), while ensuring direct contact between solid particles. In particular, it is believed that the dispersion of the conductive additives (CA) responsible for electronic conductivity can be improved (suppressing uneven distribution of conductive additives (CA) in the active material layer and uniformly configuring them), and excellent electronic conductivity can be achieved (constructing sufficient conductive paths throughout the active material layer). Therefore, the all-solid-state secondary battery incorporating this active material layer exhibits excellent cycle characteristics by suppressing battery resistance, minimizing overcurrent during charging and discharging, and preventing degradation of solid particles.
[0058] In the electrode composition of the present invention, the polymer binder (B), as described above, exhibits the function of adsorbing at least the conductive additive (CA), and also suitably adsorbing the inorganic solid electrolyte (SE) and the active substance (AC), thereby dispersing the solid particles such as the conductive additive (CA) in the dispersion medium (D) between the solid particles. Here, the adsorption of solid particles by the polymer binder (B) is not particularly limited, and includes not only physical adsorption but also chemical adsorption (adsorption through the formation of chemical bonds, adsorption through electron donation and acceptance, etc.).
[0059] On the other hand, the polymer adhesive (B) functions as a binder for bonding solid particles within the active material layer. Furthermore, it also functions as a binder for bonding the current collector and the solid particles.
[0060] As described above, the electrode composition of the present invention satisfies the following conditions (1) to (4). Each condition can be said to be satisfied by the polymer binder (B) relative to the solid particles of the inorganic solid electrolyte (SE), the active material (AC), and the conductive additive (CA), the dispersion medium (D).
[0061] The following is an explanation of each condition.
[0062] Condition (1): Dissolve the polymer binder (B) in the dispersion medium (D).
[0063] The polymer binder (B) contained in the electrode composition of the present invention exhibits the characteristic of being soluble relative to the dispersion medium (D) (solubility). Although the polymer binder (B) in the electrode composition depends on the content of the dispersion medium (D), it is generally present in the electrode composition in a state dissolved in the dispersion medium (D).
[0064] In the electrode composition containing the above-mentioned components, when conditions (1) are combined with conditions (2) to (4), the molecular chains (molecular structure) of the polymer (b) constituting the polymer binder (B) unfold in the dispersion medium (D), causing the adsorbed or nearby solid particles to repel each other and effectively suppressing aggregation. Therefore, not only can excellent initial dispersibility of the electrode composition be achieved, but also high dispersion stability can be achieved.
[0065] In this invention, the solubility of the polymer binder (B) relative to the dispersion medium (D) can be appropriately imparted by the type of polymer (b) forming the polymer binder (B) (the structure and composition of the polymer chain), the mass-average molecular weight of the polymer (b), the type or content of functional groups selected from the functional group (a) described later, and the combination with the dispersion medium (D) (e.g., the difference in SP values described later).
[0066] In this invention, "polymer binder dissolved in the dispersion medium" means that the polymer binder is dissolved in the dispersion medium of the electrode composition; for example, it means that the solubility is 10% by mass or more in a solubility determination. Conversely, "polymer binder insoluble in the dispersion medium" (insoluble) means that the solubility is less than 10% by mass in a solubility determination.
[0067] The method for determining solubility is as follows: A specified amount of the polymer binder to be tested is weighed into a glass bottle, and 100 g of a dispersion medium of the same type as the dispersion medium contained in the electrode composition is added. The mixture is stirred at 80 rpm for 24 hours at 25°C on a mixing rotor. The transmittance of the mixture obtained after 24 hours of stirring is determined under the following conditions. This test (transmittance determination) is performed by varying the amount of polymer binder dissolved (the specified amount mentioned above), and the upper limit concentration X (mass%) at which the transmittance becomes 99.8% is defined as the solubility of the polymer binder in the dispersion medium.
[0068] <Transmittance Measurement Conditions>
[0069] Dynamic light scattering (DLS) measurement
[0070] Apparatus: DLS-8000 DLS measuring device manufactured by Otsuka Electronics Co., Ltd.
[0071] Laser wavelength and output: 488nm / 100mW
[0072] Sample cell: NMR tube
[0073] Condition (2): Conductive additives in the dispersion medium (D) of the polymer adhesive (B)
[0074] Adsorption rate relative to (CA) [A] CA More than 0% and less than 50%
[0075] In the electrode composition containing the above-mentioned components, when condition (2) is combined with other conditions, excessive adsorption of the conductive additive (CA) by the polymer binder (B) is suppressed, the initial dispersibility and dispersion stability of the conductive additive (CA) are improved (collectively referred to as dispersion characteristics), and the electronic conduction pathway can be fully constructed. From the viewpoint of improving dispersion characteristics, the adsorption rate [A] CA Preferably, the adsorption rate is 2% or more, more preferably 5% or more, and even more preferably 10% or more. On the other hand, from the viewpoint of balancing high-level dispersion characteristics and the construction of electronic conduction pathways, the adsorption rate [A] is... CA The upper limit of ] is preferably 40% or less, more preferably less than 30%, and even more preferably less than 25%.
[0076] In this invention, the adsorption rate relative to the conductive additive (CA) [A] CA The type of polymer (b) forming the polymer binder (B) (structure and composition of the polymer chain), the mass-average molecular weight of the polymer (b), the type or content of functional groups selected from the functional group (a) described later, and the surface state of the conductive additive (CA) can be appropriately set.
[0077] Adsorption rate [A] CA The value is measured using the conductive additive (CA), polymer binder (B), and dispersion medium (D) contained in the electrode composition, and is an indicator of the degree to which the polymer binder (B) in the dispersion medium (D) is adsorbed onto the conductive additive (CA). Here, the adsorption of the conductive additive by the polymer binder includes not only physical adsorption but also chemical adsorption (adsorption through the formation of chemical bonds, adsorption through electron donation and acceptance, etc.).
[0078] When the electrode composition contains multiple conductive additives, the adsorption rate is set to the adsorption rate of conductive additives having the same composition (type and content) as the conductive additives in the electrode composition. Similarly, when the electrode composition contains multiple dispersion media, the adsorption rate is set to the adsorption rate of dispersion media having the same composition (type and content) as the dispersion media in the electrode composition. Furthermore, when the electrode composition contains multiple polymer binders (B), the adsorption rate is set to the adsorption rate of the multiple polymer binders.
[0079] Adsorption rate [A] CA ](%) is the value measured below.
[0080] Specifically, a 1% by mass adhesive solution was prepared by dissolving polymer adhesive (B) in dispersion medium (D). The adhesive solution and conductive additive (CA) were placed in a 15 mL vial at a mass ratio of 3:1, and stirred at 80 rpm for 1 hour at room temperature (25°C) using a mixing rotor. The mixture was then allowed to stand. The supernatant obtained from solid-liquid separation was filtered through a 1 μm filter. The filtrate was completely dried, and the mass of polymer adhesive (B) remaining in the filtrate (the mass of polymer adhesive (B) not adsorbed onto the conductive additive (CA)) W was measured. PA The mass W PA and the mass W of the polymeric adhesive (B) contained in the adhesive solution used for the determination PB The adsorption rate of the polymer binder (B) for the conductive additive (CA) was calculated using the following formula. The average adsorption rate obtained by performing this operation twice was set as the adsorption rate [A]. CA ](%).
[0081] Adsorption rate (%) = [(W)PB -W PA ) / W PB ]×100
[0082] Condition (3): The mass average molecular weight of the polymer (b) constituting the polymer adhesive (B) is 6,000 or more.
[0083] In the electrode composition containing the above-mentioned components, when condition (3) is combined with other conditions, the molecular chains (molecular structure) of the polymer (b) are widely expanded in the dispersion medium (D), which can more effectively suppress the aggregation of solid particles and further improve the dispersion characteristics. From the viewpoint of achieving further improvement in dispersion characteristics, the mass-average molecular weight of the polymer is preferably 7,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, and particularly preferably 200,000 or more. On the other hand, the mass-average molecular weight can be set to 2,000,000 or less. From the viewpoint of suppressing excessive coating on the surface of solid particles and fully constructing conduction pathways, it is preferably 1,000,000 or less, more preferably 700,000 or less, and even more preferably 600,000 or less.
[0084] The mass-average molecular weight of polymer (b) can be appropriately adjusted by changing the type and content of polymerization initiators, polymerization time, polymerization temperature, etc.
[0085] -Determination of molecular weight-
[0086] In this invention, the molecular weight of polymers and macromonomers, unless otherwise specified, refers to the mass-average molecular weight or number-average molecular weight converted from standard polystyrene obtained by gel permeation chromatography (GPC). As a method for determination, methods set to determination conditions 1 or 2 (preferred) can be generally cited. Appropriate eluents are selected and used according to the type of polymer or macromonomer.
[0087] (Measurement Condition 1)
[0088] String: Connects 2 TOSOH TSKgel Super AWM-H (product name, manufactured by TOSOH CORPORATION)
[0089] Charge carriers: 10 mM LiBr / N-methylpyrrolidone
[0090] Measurement temperature: 40℃
[0091] Carrier flow rate: 1.0 ml / min
[0092] Sample concentration: 0.1% by mass
[0093] Detector: RI (Refractive Index) Detector
[0094] (Measurement Condition 2)
[0095] Tubes: Tubes connected to TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporatio) are used.
[0096] Charge carrier: tetrahydrofuran
[0097] Measurement temperature: 40℃
[0098] Carrier flow rate: 1.0 ml / min
[0099] Sample concentration: 0.1% by mass
[0100] Detector: RI (Refractive Index) Detector
[0101] Condition (4): The presence of conductive additives in the active material layer formed by the electrode composition.
[0102] The average particle size of (CA) is less than 1.0 μm.
[0103] The above condition (4) refers to the fact that when the active material layer is formed using the electrode composition of the present invention, the average particle size of the conductive additive (CA) present in the active material layer is less than 1.0 μm. In the electrode composition containing the above components, when condition (4) is combined with other conditions, it is possible to achieve direct contact between the solid particles in the active material layer and to fully construct an electronic conduction path containing the conductive additive.
[0104] The average particle size of the conductive additive (CA) in condition (4) was determined by the method described in <Evaluation 3: Average Particle Size of Conductive Additive in Active Material Layer> in the examples described later. Furthermore, the formation conditions of the active material layer are not particularly limited; examples include those described in "Formation of Each Layer (Film Formation)" described later, such as the fabrication conditions of each electrode sheet in the examples.
[0105] From the viewpoint of further improving dispersion characteristics and constructing electronic conductive pathways, the average particle size of the conductive additive (CA) is preferably 0.8 μm or less, more preferably 0.6 μm or less, and even more preferably 0.5 μm or less. There is no particular limitation on the lower limit of the average particle size; for example, it is practically 0.05 μm, but preferably 0.1 μm or more. Furthermore, the "average particle size of the conductive additive (CA)" in the all-solid-state secondary battery electrode sheet of the present invention, described later, is also one of the preferred embodiments.
[0106] The average particle size of the conductive additive (CA) can be appropriately adjusted by varying the particle size, content, and surface state of the conductive additive (CA), as well as the type of dispersion medium or polymer binder (e.g., adjusting the difference from the SP value), and changing the content of the polymer binder. For example, increasing the content of the conductive additive (CA) tends to increase the average particle size. Conversely, increasing the content of the polymer binder tends to decrease the average particle size.
[0107] The above condition (4) is achieved by mixing the polymer binder (B), dispersion medium (D) and conductive additive (CA) in the same type and mass ratio as the electrode composition, and setting the average particle size of the conductive additive (CA) to be less than 1.0 μm (condition (4A)). This improves the dispersion characteristics of the conductive additive (CA) in the electrode composition and enables the above condition (4) to be achieved.
[0108] The average particle size of the conductive additive (CA) in condition (4A) is the average particle size measured when a dispersion is separately mixed with the polymer binder (B), dispersion medium (D), and conductive additive (CA) contained in the electrode composition in the same mass ratio (content) as that in the electrode composition. By using a separately prepared dispersion as the test object in this way, the dispersibility of the polymer binder (B) in the dispersion medium (D) relative to the conductive additive (CA) can be evaluated. The average particle size of the conductive additive (CA) in the above dispersion is a value measured by the method described in the examples described later. The preferred range of the average particle size in condition (4A) is the same as the range described in condition (4).
[0109] The electrode composition of the present invention is preferably a slurry obtained by dispersing an inorganic solid electrolyte (SE), an active substance (AC), and a conductive additive (CA) in a dispersion medium (D), especially a high-concentration slurry.
[0110] The concentration of solid components in the electrode composition of the present invention is not particularly limited and can be appropriately set. For example, at 25°C, it can be set to 20-80% by mass, preferably 30-75% by mass, and more preferably 40-70% by mass.
[0111] Because the electrode composition of the present invention exhibits excellent dispersion characteristics, it is possible to produce a high-concentration composition (slurry) with a higher solids concentration than previously possible. For example, the lower limit of the solids concentration of the high-concentration composition can be set to 50% by mass or more at 25°C, and for example, it can also be set to 60% by mass or more. The upper limit is less than 100% by mass, for example, it can be set to 90% by mass or less, preferably 85% by mass or less, and more preferably 80% by mass or less.
[0112] In this invention, solid components refer to those components that volatilize or evaporate without disappearing when the electrode composition is dried at 150°C for 6 hours under a nitrogen atmosphere and at a pressure of 1 mmHg. Typically, it refers to components other than the dispersion medium (D) described later. Furthermore, the content in the total solid components represents the content in 100% by mass of the total mass of the solid components.
[0113] The electrode composition of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition includes not only a water-free state but also a water content (also referred to as moisture content) preferably of 500 ppm or less. In the non-aqueous composition, the water content is more preferably 200 ppm or less, further preferably 100 ppm or less, and particularly preferably 50 ppm or less. If the electrode composition is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content refers to the amount of water contained in the electrode composition (mass ratio of the electrode composition), specifically, a value obtained by filtration using a 0.02 μm membrane filter and determination using Karl Fischer titration.
[0114] The electrode composition of the present invention exhibits the aforementioned excellent properties, and therefore can be preferably used as a material for forming electrode sheets for all-solid-state secondary batteries and active material layers for all-solid-state secondary batteries. In particular, it can be preferably used as a material for forming a positive electrode active material layer and a material for forming a negative electrode active material layer containing a negative electrode active material that expands and contracts significantly due to charging and discharging.
[0115] The components contained in the electrode composition of the present invention and the components that may be contained therein are described below.
[0116] <Inorganic Solid Electrolytes (SE)>
[0117] The electrode composition of the present invention contains an inorganic solid electrolyte (SE).
[0118] In this invention, inorganic solid electrolyte refers to an inorganic solid electrolyte, which is a solid electrolyte capable of allowing ions to move within it. It is clearly distinguished from organic solid electrolytes (such as polymeric electrolytes represented by polyethylene oxide (PEO) and organic electrolyte salts represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)) from the perspective of not containing organic materials as the primary ion-conducting material. Furthermore, since inorganic solid electrolytes are solid in their stable state, they generally do not dissociate or ionize into cations and anions. In this respect, they are clearly distinguished from inorganic electrolyte salts (such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), and LiCl) that dissociate or ionize into cations and anions in electrolytes or polymers. There are no particular limitations as long as the inorganic solid electrolyte possesses the ion conductivity of metals belonging to Group 1 or Group 2 of the periodic table; it generally does not possess electronic conductivity.
[0119] The inorganic solid electrolyte contained in the electrode composition of the present invention can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based inorganic solid electrolytes can be mentioned. From the viewpoint of being able to form a better interface between the active material and the inorganic solid electrolyte, a sulfide-based inorganic solid electrolyte is preferred.
[0120] In the case of the all-solid-state secondary battery of the present invention being a lithium-ion battery, it is preferable that the inorganic solid electrolyte has the ionic conductivity of lithium ions.
[0121] (i) Sulfide-based inorganic solid electrolytes
[0122] The preferred form is a sulfide-based inorganic solid electrolyte containing sulfur atoms, possessing ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and exhibiting electronic insulation properties. The preferred form is a sulfide-based inorganic solid electrolyte containing at least Li, S, and P as elements, and exhibiting lithium-ion conductivity; however, it may also appropriately contain other elements besides Li, S, and P.
[0123] As a sulfide-based inorganic solid electrolyte, for example, a lithium-ion conductive inorganic solid electrolyte that satisfies the composition represented by the following formula (S1) can be cited.
[0124] L a1 M b1 P c1 S d1 A e1 (S1)
[0125] In formula (S1), L represents an element selected from Li, Na, and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. A represents an element selected from I, Br, Cl, and F. a1 to e1 represent the composition ratio of each element, where a1:b1:c1:d1:e1 satisfies 1–12:0–5:1:2–12:0–10. a1 is preferably 1–9, more preferably 1.5–7.5. b1 is preferably 0–3, more preferably 0–1. d1 is preferably 2.5–10, more preferably 3.0–8.5. e1 is preferably 0–5, more preferably 0–3.
[0126] As described below, the composition ratio of each element can be controlled by adjusting the amount of raw material compounds used in the manufacture of sulfide-based inorganic solid electrolytes.
[0127] Sulfide-based inorganic solid electrolytes can be amorphous (glass), crystallized (glass-ceramic), or partially crystallized. For example, Li-PS-based glasses or Li-PS-based glass-ceramics containing Li, P, and S can be used.
[0128] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two of the following raw materials: lithium sulfide (Li2S), phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)), monomeric phosphorus, monomeric sulfur, sodium sulfide, hydrogen sulfide, lithium halides (e.g., LiI, LiBr, LiCl), and sulfides of the elements represented by M above (e.g., SiS2, SnS, GeS2).
[0129] The ratio of Li₂S to P₂S₅ in Li-PS-based glasses and Li-PS-based glass-ceramics is preferably 60:40 to 90:10, more preferably 68:32 to 78:22, in terms of the Li₂S:P₂S₅ molar ratio. Setting the Li₂S to P₂S₅ ratio within this range improves lithium-ion conductivity. Specifically, the lithium-ion conductivity is preferably set to 1 × 10⁻⁶. -4 S / cm or higher, more preferably 1×10 -3 S / cm or higher. Although no specific upper limit is set, it is actually 1×10⁻⁶. -1 Below S / cm.
[0130] As specific examples of sulfide-based inorganic solid electrolytes, combinations of raw materials are illustrated below. For example, Li₂S-P₂S₅, Li₂S-P₂S₅-LiCl, Li₂S-P₂S₅-H₂S, Li₂S-P₂S₅-H₂S-LiCl, Li₂S-LiI-P₂S₅, Li₂S-LiI-Li₂O-P₂S₅, Li₂S-LiBr-P₂S₅, Li₂S-Li₂O-P₂S₅, Li₂S-Li₃PO₄-P₂S₅, Li₂S-P₂S₅-P₂O₅, Li₂S-P₂S₅-SiS₂, Li₂S-P₂S₅-SiS₂-LiCl, Li₂S-P₂S₅-SnS, and Li₂S-P₂S₅-Al₂ can be cited. S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 And so on. The mixing ratio of each raw material is not limited. As a method for synthesizing sulfide-based inorganic solid electrolyte materials using this raw material composition, for example, an amorphization method can be mentioned. As an amorphization method, examples include mechanical polishing, solution processing, and melt quenching. Processing at room temperature is possible, thereby simplifying the manufacturing process.
[0131] (ii) Oxide-based inorganic solid electrolytes
[0132] Oxide-based inorganic solid electrolytes are preferably compounds containing oxygen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.
[0133] For oxide-based inorganic solid electrolytes, the preferred ionic conductivity is 1×10⁻⁶. -6 S / cm or higher, preferably 5×10 -6 S / cm or higher, especially preferably 1×10 -5 S / cm or higher. Although there is no specific upper limit, it is actually 1×10 -1 Below S / cm.
[0134] As a specific example of a compound, Li can be cited. xa La yaTiO3 [xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.] (LLT); Li xb La yb Zr zb M bb mb O nb (M bb It consists of one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn. xb satisfies 5 ≤ xb ≤ 10, yb satisfies 1 ≤ yb ≤ 4, zb satisfies 1 ≤ zb ≤ 4, mb satisfies 0 ≤ mb ≤ 2, and nb satisfies 5 ≤ nb ≤ 20. Li xc B yc M cc zc O nc (M cc It is an element selected from C, S, Al, Si, Ga, Ge, In, and Sn. xc satisfies 0 < xc ≤ 5, yc satisfies 0 < yc ≤ 1, zc satisfies 0 < zc ≤ 1, and nc satisfies 0 < nc ≤ 6. ); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, nd satisfies 3≤nd≤13.) ; Li (3-2xe) M ee xe D ee O(xe) represents a number greater than 0 and less than 0.1, M ee This represents a divalent metal atom. (D) ee Represents a halogen atom or a combination of two or more halogen atoms; Li xf Si yf O zf (xf satisfies 1 ≤ xf ≤ 5, yf satisfies 0 < yf ≤ 3, zf satisfies 1 ≤ zf ≤ 10.) ; Li xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, zg satisfies 1≤zg≤10.) ; Li3BO3; Li3BO3-Li2SO4; Li2O-B2O3-P2O5; Li2O-SiO2; Li6BaLa2Ta2O 12 Li3PO (4-3 / 2w) N w(w satisfies w < 1); Li has a LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La with a perovskite-type crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with a NASICON (Natrium super ionic conductor) crystal structure 12 Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0 ≤ xh ≤ 1, yh satisfies 0 ≤ yh ≤ 1.) ; Li7La3Zr2O with garnet-type crystal structure 12 (LLZ) etc.
[0135] Furthermore, phosphorus compounds containing Li, P, and O are preferred. Examples include lithium phosphate (Li3PO4); LiPON, in which nitrogen element replaces a portion of the oxygen element in lithium phosphate; and LiPOD. 1 (D 1 Preferably, it contains one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, and Au.
[0136] Furthermore, LiA can be preferably used. 1 ON(A 1 It consists of one or more elements selected from Si, B, Ge, Al, C, and Ga.
[0137] (iii) Halogen-based inorganic solid electrolytes
[0138] Halogen-based inorganic solid electrolytes are preferably compounds containing halogen atoms, possessing conductivity of ions belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.
[0139] There are no particular limitations on the type of inorganic solid electrolyte, such as LiCl, LiBr, LiI, and compounds like Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among these, Li3YBr6 and Li3YCl6 are preferred.
[0140] (iv) Hydride-based inorganic solid electrolytes
[0141] Hydride-based inorganic solid electrolytes are preferably compounds containing hydrogen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.
[0142] As a hydride-based inorganic solid electrolyte, there are no particular limitations; examples include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0143] The inorganic solid electrolyte contained in the electrode composition of the present invention is preferably in particulate form. The shape of the particles is not particularly limited and can be flat, amorphous, etc., but is preferably spherical or granular. When the inorganic solid electrolyte is in particulate form, the particle size (volume average particle size: D) of the inorganic solid electrolyte is... 50 There are no particular limitations, but it is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more. As an upper limit, it is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 10 μm or less.
[0144] The particle size of the inorganic solid electrolyte was determined using the following steps. A 1% (w / w) dispersion of the inorganic solid electrolyte particles was prepared by diluting the particles in a 20 mL sample vial with water (or heptane if water is unstable). The diluted dispersion sample was irradiated with ultrasound at 1 kHz for 10 minutes and then immediately used in the test. Using this dispersion sample, 50 data acquisitions were performed using a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) at 25°C using a measuring quartz cell to obtain the volume average particle size. Other detailed conditions were referenced as needed in Japanese Industrial Standard (JIS) Z8828:2013 "Particle Size Analysis - Dynamic Light Scattering Method". Five samples were prepared for each grade, and their average value was used.
[0145] There are no particular limitations on the method for adjusting the particle size; well-known methods can be used, such as the use of conventional pulverizers or classifiers. For example, mortars, ball mills, sand mills, vibratory ball mills, satellite ball mills, planetary ball mills, rotary airflow mills, or sieves can be appropriately used. During pulverization, wet pulverization with a dispersion medium such as water or methanol can be appropriately performed. To achieve the desired particle size, classification is preferred. Classification is not particularly limited; sieves, air classifiers, etc., can be used. Both dry and wet classification can be used.
[0146] The electrode composition may contain one or more inorganic solid electrolytes.
[0147] The content of inorganic solid electrolyte in the electrode composition is not particularly limited and can be appropriately determined. From the viewpoint of dispersion characteristics, it is preferable that the total content of the solid component (including the active material) is 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more, out of 100% by mass. As an upper limit, from the same viewpoint, it is preferable that it is 99.9% by mass or less, more preferably 99.5% by mass or less, and particularly preferably 99% by mass or less.
[0148] <Active Substances (AC)>
[0149] The electrode composition of the present invention contains an active substance capable of intercalating and deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table.
[0150] As active materials (AC), positive electrode active materials and negative electrode active materials can be listed.
[0151] (Positive electrode active material)
[0152] The positive electrode active material is an active material capable of intercalating and deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material capable of reversibly intercalating and deintercalating lithium ions. There are no particular limitations as long as the material has the above-mentioned properties, and it can be a transition metal oxide from a decomposition battery or an element that can recombine with Li, such as sulfur.
[0153] Among them, transition metal oxides are preferred as positive electrode active materials, and more preferably materials containing the transition metal element M. a A transition metal oxide (selected from one or more elements including Co, Ni, Fe, Mn, Cu, and V). Furthermore, element M may also be mixed into this transition metal oxide. b (Elements of Group 1(Ia) and Group 2(IIa) of the periodic table, excluding lithium, and elements such as Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B). As a mixing amount, it is preferable to be relative to the transition metal element M. a The amount (100 mol%) is 0-30 mol%. More preferably, it is Li / M a They are synthesized by mixing in a molar ratio of 0.3 to 2.2.
[0154] Specific examples of transition metal oxides include (MA) transition metal oxides with a layered rock salt structure, (MB) transition metal oxides with a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0155] Specific examples of transition metal oxides (MA) with layered rock salt-type structures include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), and LiNi 0.85 Co 0.10 Al 0.05 O2 (lithium nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0156] Specific examples of transition metal oxides (MB) with spinel-type structures include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.
[0157] Examples of lithium-containing transition metal phosphates (MC) include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate).
[0158] Examples of lithium-containing transition metal halophosphates (MD) include, for example, iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0159] Examples of lithium-containing transition metal silicate compounds include, for example, Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0160] In this invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.
[0161] The positive electrode active material contained in the electrode composition of the present invention is preferably in particulate form. The shape of the particles is not particularly limited and can be flat, amorphous, etc., but is preferably spherical or granular. When the positive electrode active material is in particulate form, the particle size (volume average particle size) of the positive electrode active material is not particularly limited; for example, it is preferably 0.1 to 50 μm, more preferably 0.5 to 10 μm. The particle size of the positive electrode active material can be adjusted in the same way as the particle size of the inorganic solid electrolyte described above, and its measurement method can also be the same as that for the inorganic solid electrolyte.
[0162] Positive active materials obtained by sintering can also be used after being cleaned with water, acidic aqueous solutions, alkaline aqueous solutions, and organic solvents.
[0163] The electrode composition of the present invention may contain one or more positive active substances.
[0164] The content of the positive electrode active material in the electrode composition is not particularly limited and can be appropriately determined. For example, in 100% by mass of the solid content, it is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, even more preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass.
[0165] (Negative electrode active material)
[0166] The negative electrode active material is an active material capable of intercalating and deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table, preferably an active material capable of reversibly intercalating and deintercalating lithium ions. There are no particular limitations on the material as long as it possesses the aforementioned properties; examples include carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, and negative electrode active materials capable of forming alloys with lithium (capable of alloying). From a reliability perspective, carbonaceous materials, metal composite oxides, or lithium monomers are preferred. From the viewpoint of enabling high-capacity all-solid-state secondary batteries, active materials capable of alloying with lithium are preferred.
[0167] Carbonaceous materials used as negative electrode active materials refer to materials that are essentially composed of carbon. Examples include carbonaceous materials produced by sintering petroleum asphalt, carbon black such as acetylene black (AB), graphite (natural graphite, vapor-grown graphite, and other artificial graphite), and various synthetic resins such as PAN (polyacrylonitrile) resins or furfuryl alcohol resins. Furthermore, examples include various types of carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as mesophase microspheres, graphite whiskers, and planar graphite.
[0168] These carbonaceous materials are classified into non-graphitized carbonaceous materials (also known as hard carbon) and graphite-based carbonaceous materials based on the degree of graphitization. Furthermore, the carbonaceous materials preferably possess the facet spacing or density and crystallite size described in Japanese Patent Application Publication Nos. 62-22066, 2-6856, and 3-45473. The carbonaceous material need not be a single material; mixtures of natural and artificial graphite as described in Japanese Patent Application Publication No. 5-90844, or coated graphite as described in Japanese Patent Application Publication No. 6-4516, etc., can also be used.
[0169] As a carbonaceous material, hard carbon or graphite is preferred, with graphite being more preferred.
[0170] As oxides of metals or half-metals suitable as negative electrode active materials, there are no particular limitations as long as they are oxides capable of absorbing and releasing lithium. Examples include oxides of metal elements (metal oxides), composite oxides of metal elements, or composite oxides of metal elements and half-metal elements (collectively referred to as metal composite oxides), and oxides of half-metal elements (half-metal oxides). Among these oxides, amorphous oxides are preferred, and further preferred are chalcogenides, the reaction products of metal elements with elements of Group 16 of the periodic table. In this invention, a half-metal element refers to an element exhibiting intermediate properties between a metal element and a non-half-metal element, typically including six elements: boron, silicon, germanium, arsenic, antimony, and tellurium, and further including three elements: selenium, polonium, and astatine. Furthermore, amorphous means having a broad scattering band with vertices in the region of 20° to 40° at 2θ using CuKα X-ray diffraction, and may also have crystalline diffraction lines. The strongest intensity of the crystalline diffraction lines appearing in the region of 40° to 70° at a 2θ value is preferably 100 times or less than the intensity of the diffraction line at the apex of the broad scattering band appearing in the region of 20° to 40° at a 2θ value, more preferably 5 times or less, and especially preferably a non-crystalline diffraction line.
[0171] Among the compounds comprising the aforementioned amorphous oxides and chalcogenides, amorphous oxides of half-metallic elements or the aforementioned chalcogenides are more preferred, and (composite) oxides or chalcogenides comprising one or more elements selected from groups 13(IIIB) to 15(VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga₂O₃, GeO, PbO, PbO₂, Pb₂O₃, Pb₂O₄, Pb₃O₄, Sb₂O₄, Sb₂O₈Bi₂O₃, Sb₂O₈Si₂O₃, Sb₂O₅, Bi₂O₃, Bi₂O₄, GeS, PbS, PbS₂, Sb₂S₃, or Sb₂S₅.
[0172] As a negative electrode active material that can be used with amorphous oxides centered on Sn, Si, and Ge, carbonaceous materials, lithium monomers, lithium alloys, and negative electrode active materials that can be alloyed with lithium are preferred examples.
[0173] From the viewpoint of high current density charge and discharge characteristics, oxides of metal or half-metal elements, especially metal (composite) oxides and the aforementioned chalcogenides, preferably contain at least one of titanium and lithium as constituent components. Examples of lithium-containing metal composite oxides (lithium composite metal oxides) include composite oxides of lithium oxide with the aforementioned metal (composite) oxides or chalcogenides; more specifically, Li₂SnO₂ can be cited.
[0174] The negative electrode active material, such as a metal oxide, preferably contains titanium (titanium oxide). Specifically, due to Li4Ti5O 12 Lithium titanate (LTO) exhibits minimal volume change during lithium ion adsorption and deintercalation, resulting in excellent rapid charge and discharge characteristics. It is preferred in terms of both suppressing electrode degradation and improving the lifespan of lithium-ion secondary batteries.
[0175] There are no particular restrictions on the lithium alloy used as the negative electrode active material, as long as it is an alloy commonly used as the negative electrode active material in secondary batteries. For example, lithium-aluminum alloys can be cited. Specifically, lithium-aluminum alloys can be cited, which are made by adding 10% by mass of aluminum to lithium as the base metal.
[0176] There are no particular limitations on the negative electrode active material that can form an alloy with lithium, as long as it is a negative electrode active material commonly used in secondary batteries. Such active materials experience significant expansion and contraction due to charging and discharging in all-solid-state secondary batteries, which accelerates the decline in cycle characteristics. However, the electrode composition of the present invention contains the aforementioned components and satisfies the aforementioned conditions, thus suppressing the decline in cycle characteristics. Examples of such active materials include (negative electrode) active materials (alloys, etc.) containing silicon or tin, and various metals such as Al and In. Preferably, negative electrode active materials containing silicon (silicon-containing active materials) are preferred, as they enable higher battery capacity. More preferably, silicon-containing active materials have a silicon content of 50 mol% or more of all constituent elements.
[0177] Generally, negative electrodes containing these active materials (e.g., Si negative electrodes containing silicon-containing active materials, Sn negative electrodes containing tin-containing active materials, etc.) can absorb more Li ions compared to carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions retained per unit mass increases. Therefore, the battery capacity (energy density) can be increased. Consequently, it has the advantage of extending battery operating time.
[0178] Examples of silicon-containing active materials include Si and SiO. xSilicon materials such as (0 < x ≤ 1), and silicon-containing alloys (e.g., LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or structured active materials (e.g., LaSi2 / Si) containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc.), as well as active materials containing silicon elements such as SnSiO3 and SnSiS3, and tin elements. Additionally, SiO... x It can be used as a negative electrode active material (semi-metal oxide), and Si is generated through the operation of an all-solid-state secondary battery, so it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.
[0179] Examples of anode active materials containing tin include those containing Sn, SnO, SnO2, SnS, SnS2, and the aforementioned silicon and tin elements. Furthermore, composite oxides with lithium oxide, such as Li2SnO2, can also be cited.
[0180] In this invention, the above-mentioned negative electrode active material can be used without particular limitations. However, from the viewpoint of battery capacity, it is preferable to use a negative electrode active material that can be alloyed with lithium. More preferably, it is the above-mentioned silicon material or silicon-containing alloy (an alloy containing silicon element). It is even more preferably to contain silicon (Si) or a silicon-containing alloy.
[0181] The negative electrode active material contained in the electrode composition of the present invention is preferably in particulate form. The shape of the particles is not particularly limited and can be flat, amorphous, etc., but is preferably spherical or granular. When the negative electrode active material is in particulate form, the particle size (volume average particle size) of the negative electrode active material is not particularly limited; for example, it is preferably 0.1 to 60 μm, more preferably 0.5 to 10 μm. The particle size of the negative electrode active material can be adjusted in the same way as the particle size of the inorganic solid electrolyte described above, and its measurement method can also be the same as that for the inorganic solid electrolyte.
[0182] The electrode composition of the present invention may contain one or more negative electrode active substances.
[0183] The content of the negative electrode active material in the electrode composition is not particularly limited and can be appropriately determined. For example, in 100% by mass of the solid content, it is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, even more preferably 30 to 80% by mass, and even more preferably 40 to 75% by mass.
[0184] As a determination method, inductively coupled plasma (ICP) emission spectroscopy can be used. As a simple method, the chemical formula of the compound obtained by the above-mentioned firing method can be calculated from the mass difference of the powder before and after firing.
[0185] (Coating of active substances)
[0186] The surfaces of the positive and negative electrode active materials can also be coated with different metal oxides. Examples of surface coating agents include metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li. Specifically, examples include spinel titanate, tantalum oxides, niobium oxides, and lithium niobate compounds; for instance, Li₄Ti₅O₅ can be used. 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.
[0187] Furthermore, the electrode surface containing positive or negative active materials can be surface-treated with sulfur or phosphorus.
[0188] Furthermore, the particle surface of the positive or negative active material can be surface-treated by photochemical rays or active gas (plasma, etc.) before and after the aforementioned surface coating.
[0189] <Conductive Additive (CA)>
[0190] The electrode composition of the present invention contains a conductive additive.
[0191] There are no particular restrictions on the conductive additives used; any conductive additives known to be used as conductive additives can be used. For example, they can be graphite materials such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, and furnace black, amorphous carbon such as needle coke, carbon fiber materials such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, metal powders such as copper and nickel, metal fibers, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.
[0192] In this invention, when active materials and conductive additives are used in combination, the conductive additives that do not produce the insertion and extraction of metal ions (preferably Li ions) belonging to Group 1 or Group 2 of the periodic table during battery charging and discharging, and do not function as active materials, are classified as conductive additives. Therefore, among conductive additives, those that can function as active materials in the active material layer during battery charging and discharging are classified as active materials rather than conductive additives. Whether an additive functions as an active material during battery charging and discharging is determined by its combination with active materials, rather than by a general rule.
[0193] The conductive additive contained in the electrode composition of the present invention is preferably in particulate form. The shape of the particles is not particularly limited and can be flat, amorphous, etc., but is preferably spherical or granular. When the conductive additive is in particulate form, the particle size (volume average particle size) is not particularly limited; for example, it is preferably 0.02 to 1.0 μm, more preferably 0.02 μm or more and less than 1.0 μm, and even more preferably 0.03 to 0.5 μm. The particle size of the conductive additive can be adjusted in the same way as the particle size of the inorganic solid electrolyte described above, and its measurement method can also be the same as that for the particle size of the inorganic solid electrolyte.
[0194] The electrode composition of the present invention may contain one or more conductive additives.
[0195] The content of the conductive additive in the electrode composition is not particularly limited and can be appropriately determined. For example, in 100% by mass of the solid content, it is preferably more than 0% by mass and less than 10% by mass, more preferably 1.0 to 5.0% by mass, and even more preferably 1.0 to 2.0% by mass.
[0196] <Polymer Adhesives (B)>
[0197] The electrode composition of the present invention may contain one or more polymer binders (B). As long as the polymer binder (B) meets conditions (1) to (4), other properties are not particularly limited and can be appropriately set.
[0198] Preferred properties or physical characteristics of the polymer adhesive (B) and the polymer (b) constituting the polymer adhesive (B) are described.
[0199] (Preferred physical properties or characteristics of polymer adhesive (B) and polymer (b))
[0200] The polymer binder (B) preferably exhibits an adsorption rate of less than 45% relative to the inorganic solid electrolyte (SE) in the dispersion medium (D) contained in the electrode composition. [A] SE ].
[0201] In an electrode composition containing the above-mentioned components and satisfying the above-mentioned conditions, when the polymer binder (B) further satisfies the above-mentioned adsorption rate [A] SE When [the adsorption rate is high], in addition to the conductive additive (CA), it is also over-adsorbed onto the inorganic solid electrolyte (SE), which can improve the dispersibility of the inorganic solid electrolyte (SE) and further improve the dispersion characteristics of the electrode composition, thus fully constructing the conduction pathway. From the perspective of further improving the dispersion characteristics of the electrode composition and constructing the conduction pathway, the adsorption rate [A] SE Preferably, the adsorption rate is 40% or less, more preferably 35% or less, and even more preferably 30% or less. On the other hand, the adsorption rate [A]SE The lower limit of ] is actually 0% or more, for example, preferably 5% or more, and more preferably 10% or more.
[0202] In this invention, the adsorption rate relative to the inorganic solid electrolyte (SE) [A] SE The polymer (b) forming the polymer binder (B) can be appropriately set by the type of polymer (structure and composition of polymer chains), the mass-average molecular weight of polymer (b), the type or content of functional groups selected from the functional group (a) described later, and the surface state of the inorganic solid electrolyte (SE).
[0203] Adsorption rate [A] SE The adsorption rate of inorganic solid electrolyte (SE) in the dispersion medium (D) of the polymer binder (B) is a value measured using the inorganic solid electrolyte (SE), polymer binder (B), and dispersion medium (D) contained in the electrode composition. It is an indicator of the degree of adsorption of the polymer binder (B) relative to the inorganic solid electrolyte (SE) in the dispersion medium (D). Here, the adsorption of inorganic solid electrolyte (SE) by the polymer binder (B) includes not only physical adsorption but also chemical adsorption (adsorption through the formation of chemical bonds, adsorption through electron donation and acceptance, etc.).
[0204] When the electrode composition contains multiple inorganic solid electrolytes, the adsorption rate is defined as the adsorption rate for inorganic solid electrolytes having the same composition (type and content) as the inorganic solid electrolytes in the electrode composition. Similarly, when the electrode composition contains multiple dispersion media, the adsorption rate is defined as the adsorption rate for dispersion media having the same composition (type and content) as the dispersion media in the electrode composition. Furthermore, when the electrode composition uses multiple polymer binders, the adsorption rate is also defined as the adsorption rate for each polymer binder.
[0205] Adsorption rate [A] SE The percentage was determined using the inorganic solid electrolyte (SE), polymer binder (B), and dispersion medium (D) used to prepare the electrode composition, as follows.
[0206] Specifically, a 1% by mass adhesive solution was prepared by dissolving polymer adhesive (B) in dispersion medium (D). The adhesive solution and inorganic solid electrolyte (SE) were placed in a 15 mL vial at a mass ratio of 42:1, stirred at 80 rpm for 1 hour at room temperature (25°C) using a mixing rotor, and then allowed to stand. The supernatant obtained from solid-liquid separation was filtered through a 1 μm filter, and the filtrate was completely dried. The mass of polymer adhesive (B) remaining in the filtrate (the mass of polymer adhesive (B) not adsorbed onto the inorganic solid electrolyte (SE)) W was measured.A The mass W A and the mass W of the polymeric adhesive (B) contained in the adhesive solution used for the determination B The adsorption rate of the polymer binder (B) for the inorganic solid electrolyte (SE) was calculated using the following formula. The average adsorption rate obtained by performing this operation twice was taken as the adsorption rate [A]. SE ](%).
[0207] Adsorption rate (%) = [(W) B -W A ) / W B ]×100
[0208] In polymer (b), from the viewpoint of improving affinity with polymer binder (B) and dispersion medium (D) and dispersion characteristics of solid particles, its SP value is preferably 10 to 24 MPa, for example. 1 / 2 More preferably 14–22 MPa 1 / 2 More preferably 16-20 MPa 1 / 2 .
[0209] The method for calculating SP values is explained.
[0210] (1) Calculate the SP value of the structural unit.
[0211] First, for polymer (b), the structural units with specified SP values are determined.
[0212] For example, when calculating the SP value of polymer (b), if the polymer is a chain polymer, it is set as a structural unit that is the same as the constituent component derived from the raw material compound.
[0213] Next, unless otherwise stated, the SP value for each structural element is determined using the Hoy method (refer to HL Hoy Journal of Paint Technology Vol. 42, No. 541, 1970, 76-118 and Polymer Handbook 4). th Chapter 59, VII, page 686, Tables 5 and 6, and the following formula in Table 6).
[0214] [Formula 1]
[0215]
[0216] In the formula, δ t Indicates the SP value. F t Molar attraction function (J×cm) 3 ) 1 / 2 mol,
[0217] It is expressed by the following formula. V is the molar volume (cm³). 3 / mol), represented by the following formula. It is represented by the following formula.
[0218] F t =Σn i F t,i V=Σn i V i
[0219]
[0220] In the above formula, F t,i V represents the molar gravitational function of each structural unit. i Δ represents the molar volume of each structural unit. (P) t,i n represents the correction value for each structural element. i This indicates the number of each structural unit.
[0221] (2) SP value of polymer (b)
[0222] Using the structural units determined as described above and the calculated SP values, the SP value of polymer (b) is calculated using the following formula. Additionally, the SP values of the structural units obtained from the aforementioned literature are converted to SP values (unit: MPa). 1 / 2 (For example, 1cal) 1 / 2 cm -3 / 2 ≈2.05J 1 / 2 cm -3 / 2 ≈2.05MPa 1 / 2 And use it.
[0223] SP p 2 =(SP1) 2 ×W1)+(SP2 2 ×W2)+……
[0224] In the formula, SP1, SP2... represent the SP values of the structural unit, and W1, W2... represent the mass fraction of the structural unit.
[0225] In this invention, the mass fraction of the structural unit is the mass fraction of the polymer corresponding to the constituent component (the raw material compound into which the constituent component is introduced) of the structural unit.
[0226] The SP value of polymer (b) can be adjusted according to the type or composition of polymer (b) (the type and content of constituent components).
[0227] From the viewpoint of achieving higher dispersion characteristics, it is preferable that the polymer (b) has an SP value that satisfies the range described below and the difference (absolute value) between the SP value and the SP value of the dispersion medium (D).
[0228] The moisture concentration of polymer (b) is preferably below 100 ppm (by mass). Furthermore, this polymer can be crystallized and dried, or a polymer solution can be used directly.
[0229] Polymer (b) is preferably amorphous. In this invention, "amorphous" polymer typically means that no endothermic peak due to crystal melting is observed when measured at the glass transition temperature.
[0230] Polymer (b) can be a non-crosslinked polymer or a crosslinked polymer. Furthermore, when crosslinking polymer (b) is performed by heating or applying voltage, it is preferable that the polymer (b) before crosslinking has a mass-average molecular weight within the range specified by the above condition (3), and it is even more preferable that the polymer (b) at the start of use of the all-solid-state secondary battery also has a mass-average molecular weight within the range specified by the above condition (3).
[0231] From the viewpoint of dispersion characteristics and coating suitability, as well as suppressing the degradation of battery characteristics, it is preferable that the polymer (b) and the polymer binder (B) do not react with the inorganic solid electrolyte during the heating process in the preparation of the electrode composition, the fabrication of the electrode sheet for all-solid-state secondary batteries, or the manufacturing of all-solid-state secondary batteries. Specifically, it is preferable that they do not have intramolecular olefinic double bonds. In this invention, the absence of intramolecular olefinic double bonds in the polymer includes the following: the polymer has olefinic double bonds within a range that does not impair the effects of this invention, for example, in an amount (based on nuclear magnetic resonance spectroscopy (NMR)) of 0.1% or less.
[0232] (Polymer(b))
[0233] As long as the polymer (b) satisfies the above condition (3) and is a polymer adhesive (B) that satisfies the above conditions (1), (2) and (4), there are no particular restrictions on its type and composition, as well as the bonding mode (arrangement) of the constituent components constituting the main chain, and various polymers that can be used as adhesive polymers for all-solid-state secondary batteries can be used.
[0234] As polymer (b), polymers having at least one type of bond selected from urethane bonds, urea bonds, amide bonds, imide bonds, and ester bonds, or carbon-carbon double bonds in the main chain are preferred examples. More specifically, polymers having urethane bonds, urea bonds, amide bonds, imide bonds, or ester bonds in the main chain are, for example, step-growth polymers (condensation, addition, or addition condensation) such as polyurethanes, polyureas, polyamides, polyimides, and polyesters. Furthermore, polymers having carbon-carbon double bonds in the main chain are, for example, chain polymers such as fluoropolymers (fluorinated polymers), hydrocarbon polymers, vinyl polymers, and (meth)acrylic acid polymers. The bonding mode of the main chain in these polymers is not particularly limited and can be any of random bonding (random polymers), alternating bonding (alternating polymers), block bonding (block polymers), or graft bonding (graft polymers).
[0235] Preferably, the polymer is a chain polymer, more preferably a hydrocarbon polymer, a vinyl polymer, or a (meth)acrylic acid polymer, and even more preferably a (meth)acrylic acid polymer. Furthermore, the bonding mode of the main chain is preferably random bonding or block bonding.
[0236] The polymer (b) constituting the polymer adhesive (B) may be one type or two or more types. When the polymer adhesive (B) is composed of two or more polymers (b), it is preferable that at least one polymer is a chain polymer, and more preferably all polymers are chain polymers.
[0237] In this invention, the polymer backbone refers to all linear molecular chains that constitute the polymer and can be considered branches or side groups relative to the backbone. While depending on the mass-average molecular weight of the branches or side groups, typically the longest chain in the polymer becomes the backbone. However, terminal groups at the ends of the polymer are not included in the backbone. Furthermore, polymer side chains refer to molecular chains other than the backbone, including both short and long chains.
[0238] There are no particular limitations on the constituent components that form polymer (b). Examples include constituent components having functional groups (a) selected from functional group (a), constituent components having substituents with 8 or more carbon atoms as side chains, macromonomer constituent components, and other constituent components. In addition, when the polymer chain of a macromonomer constituent component contains a constituent component having functional group (a) as a polymer chain constituent component, the macromonomer constituent component is equivalent to a constituent component having functional groups selected from functional group (a).
[0239] The following describes the constituent components of polymer (b).
[0240] (Constitutes having functional groups selected from functional group (a))
[0241] Polymer (b) preferably contains one or more constituent components having functional groups (including bonding) selected from the functional group (a) below. When polymer (b) contains constituent components having such functional groups (hereinafter, sometimes referred to as constituent components containing functional groups), the polymer binder (B) can exhibit suitable adsorption force relative to solid particles such as conductive additives (CA) and improve the dispersion characteristics of the electrode composition.
[0242] The constituent component can be any component that forms polymer (b). Functional groups can be incorporated into the polymer backbone or into the side chains. When incorporated into the side chains, the functional groups can be directly bonded to the backbone or bonded via a linker. There are no particular limitations on the linker; examples of linkers L described later can be cited. F .
[0243] <Functional Groups (a)>
[0244] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, ether (-O-), imino (=NR, -NR-), ester (-CO-O-), amide (-CO-NR-), carbamate (-NR-CO-O-), urea (-NR-CO-NR-), heterocyclic, aryl, carboxylic anhydride
[0245] The amino, sulfonyl, phosphate (phosphonyl), phosphonic acid, heterocyclic, and aryl groups included in functional group (a) are not particularly limited, and have the same meaning as the corresponding groups of substituent Z described later. The amino group preferably has 0 to 12 carbon atoms, more preferably 0 to 6, and especially preferably 0 to 2. When amino, ether, imino (-NR-), ester, amide, carbamate, or urea bonds are included in a ring structure, it is classified as a heterocycle. Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, and thioalkyl groups can form salts. Examples of salts include various metal salts, ammonium salts, or amine salts.
[0246] In chain polymers, components having ester bonds (excluding ester bonds that form carboxyl groups) or amide bonds refer to components whose ester bonds or amide bonds are not directly bonded to atoms of the main chain constituting the chain polymer, or to atoms of the main chain constituting the polymer chain as a branch or comb chain (e.g., the polymer chain possessed by macromonomers). For example, components not containing alkyl methacrylates.
[0247] The chemical formula in parentheses following the name of each bond, such as ether bonds, indicates the chemical structure of that bond. There are no particular restrictions on the terminal groups bonded to these groups; groups selected from substituent Z described later can be included, for example, alkyl groups. R in each bond represents a hydrogen atom or a substituent, preferably a hydrogen atom. There are no particular restrictions on the substituents; they are selected from substituent Z described later, preferably alkyl groups. Furthermore, ether bonds are included in carboxyl groups, hydroxyl groups, etc., but the -O- groups contained in these are not considered ether bonds.
[0248] There are no particular limitations on the carboxylic anhydride group, including groups formed by removing one or more hydrogen atoms from a dicarboxylic anhydride (e.g., groups represented by formula (2a) below), and constituent components themselves formed by copolymerizing polymerizable dicarboxylic anhydrides into copolymerizable compounds (e.g., constituent components represented by formula (2b) below). Groups formed by removing one or more hydrogen atoms from a dicarboxylic anhydride are preferably groups formed by removing one or more hydrogen atoms from a cyclic dicarboxylic anhydride. Examples of dicarboxylic anhydrides include, for example, acyclic dicarboxylic anhydrides such as acetic anhydride, propionic anhydride, and benzoic acid rod, and cyclic dicarboxylic anhydrides such as maleic anhydride, phthalic anhydride, fumaric acid rod, succinic anhydride, and itaconic anhydride. There are no particular limitations on polymerizable dicarboxylic anhydrides, and dicarboxylic anhydrides having unsaturated bonds within the molecule are possible examples, with polymerizable cyclic dicarboxylic anhydrides being preferred. Specifically, maleic anhydride and itaconic anhydride are examples. Carboxylic anhydride groups derived from cyclic dicarboxylic anhydrides are also equivalent to heterocyclic groups, but are classified as carboxylic anhydride groups in this invention.
[0249] Examples of carboxylic anhydride groups include groups represented by formula (2a) or constituents represented by formula (2b), but the invention is not limited to these. In each formula, * indicates a bonding position.
[0250] [Chemical Formula 1]
[0251]
[0252] A constituent containing functional groups may have one or more functional groups. When it has two or more functional groups, they may or may not be bonded to each other.
[0253] From the viewpoint of adsorption and dispersion properties with solid particles, especially conductive additives (CA), the functional groups are preferably carboxyl, hydroxyl, or carboxylic anhydride groups. When the constituent containing functional groups has two or more functional groups, the two or more functional groups contained in functional group (a) can be appropriately combined, but from the viewpoint of adsorption and dispersion properties, combinations of ether bonds and aryl groups, combinations of carboxyl and hydroxyl groups, combinations of carboxyl and carboxylic anhydride groups, and combinations of carboxyl, hydroxyl, or carboxylic anhydride groups are preferred.
[0254] Preferably, the aforementioned functional groups are incorporated into the side chain of polymer (b). In this case, as a component containing functional groups, examples include components that have the aforementioned functional groups in a portion of the main chain directly or via a linking group, or components that have polymer chains in which the aforementioned functional groups are incorporated as substituents in a portion of the main chain of polymer (b) directly or via a linking group.
[0255] The following describes the components that have the above-mentioned functional groups in the part of the structure that are directly or via linking groups incorporated into the main chain, and the components that have polymer chains will be described later.
[0256] In a constituent component with functional groups, the portion of the structure incorporated into the main chain is not uniquely determined based on the type of polymer (B) and can be appropriately selected. For example, in the case of chain polymers, carbon chains (carbon-carbon bonds) can be cited.
[0257] As a connecting base L, which connects the partial structure incorporated into the main chain and the aforementioned functional groups. F There are no particular limitations; examples include alkylene groups (preferably 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3), alkenyl groups (preferably 2 to 6 carbon atoms, more preferably 2 to 3), aryl groups (preferably 6 to 24 carbon atoms, more preferably 6 to 10), oxygen atoms, sulfur atoms, and imino groups (-NR). N -:R N This refers to a group consisting of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. Other related groups include carbonyl groups, phosphate linkages (-OP(OH)(O)-O-), phosphonic acid linkages (-P(OH)(O)-O-), or combinations thereof. Preferably, the linkage is a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, and an imino group; more preferably, it contains a -CO-O- group or a -CO-N(R) group. N )-base(R N As described above, the group is particularly preferred to be -CO-O- or -CO-N(R) N )-base(R N As described above, it is a group composed of alkylene groups.
[0258] In this invention, the connecting base L is formed F The number of atoms is preferably 1 to 36, more preferably 1 to 24, even more preferably 1 to 12, and particularly preferably 1 to 6. Connecting group L F The number of connecting atoms is preferably 12 or less, more preferably 10 or less, and particularly preferably 8 or less. A lower limit is 1 or more. The above-mentioned number of connecting atoms refers to the minimum number of atoms connecting the specified structural parts. For example, in the case of -C(=O)-O-, the connecting base L... FThe number of atoms becomes 3, but the number of connected atoms becomes 2.
[0259] Partial structure and linker L incorporated into the main chain F Substituents other than the functional groups described above may be present. There are no particular limitations on such substituents; for example, groups selected from substituents Z described later may be included, and groups other than those in functional group (a) are preferred.
[0260] There are no particular limitations on the compounds that lead to the aforementioned functional group-containing constituents (also called compounds with functional groups). Examples include compounds having at least one carbon-carbon unsaturated bond and the aforementioned functional group. For instance, compounds containing a carbon-carbon unsaturated bond directly bonded to the aforementioned functional group, or compounds where the carbon-carbon unsaturated bond and the aforementioned functional group are linked via a linker L... F Compounds formed by bonding, and compounds in which the functional groups themselves contain carbon-carbon unsaturated bonds (e.g., the aforementioned polymeric cyclic dicarboxylic anhydrides). Furthermore, compounds having the aforementioned functional groups include compounds capable of introducing the functional groups into the constituent components of the polymerized product through various reactions (e.g., compounds (including polymers) capable of undergoing addition or condensation reactions with constituent components derived from carboxylic anhydrides, constituent components having carbon-carbon unsaturated bonds, etc.). In addition, compounds having the aforementioned functional groups also include macromonomers whose carbon-carbon unsaturated bonds are incorporated as substituents into the functional groups in the polymer chain directly or via a linker L. F Compounds formed by bonding.
[0261] The constituent containing the aforementioned functional groups is not particularly limited as long as it has the aforementioned functional groups. Examples include (meth)acrylic acid compound (M1) or other polymeric compound (M2) described later, constituents represented by any one of formulas (b-1) to (b-3) described later, and constituents represented by formula (1-1) described later incorporating the aforementioned functional groups. Specific examples of the constituents containing the aforementioned functional groups include constituents in the exemplary polymers described later and the polymers synthesized in the examples, but the present invention is not limited to these.
[0262] There are no particular limitations on the compounds having the aforementioned functional groups. Examples include polymerizable cyclic dicarboxylic anhydrides and short-chain alkyl (meth)acrylate compounds (short-chain alkyl refers to alkyl groups with 3 or fewer carbon atoms). Furthermore, examples of compounds in which the aforementioned functional groups are introduced into polymerizable cyclic dicarboxylic anhydrides include dicarboxylic acid monoester compounds obtained by reacting maleic anhydride compounds with alcohols, etc., in an addition reaction (ring-opening reaction).
[0263] From the viewpoint of the dispersion characteristics and adsorption properties of the polymer binder (B), the total content of the constituent components containing the above-mentioned functional groups in the polymer (b) is preferably 0.01 to 40% by mass, more preferably 0.02 to 30% by mass, even more preferably 0.05 to 20% by mass, particularly preferably 0.1 to 10% by mass, and most preferably 0.2 to 8% by mass.
[0264] When polymer (b) has multiple functional group-containing components, the total content of the functional group-containing components is defined as the sum of the contents of each component. Furthermore, even if a single component has multiple functional groups, the content of the functional group-containing component generally refers to the content of that single component. In addition, the total content of the functional group-containing components also includes, as described later, the content of components with polymer chains incorporating the aforementioned functional groups as substituents (macromonomer components).
[0265] When polymer (b) has multiple functional group-containing components (including macromonomer components), the content of the functional group-containing components is appropriately determined taking into account the total content mentioned above. For example, when polymer (b) has two functional group-containing components, the content of one functional group-containing component is preferably 0.005 to 30% by mass, more preferably 0.01 to 20% by mass, even more preferably 0.05 to 8% by mass, and particularly preferably 0.1 to 3% by mass. The content of the other functional group-containing component is preferably 0.005 to 10% by mass, more preferably 0.01 to 10% by mass, and even more preferably 0.05 to 2% by mass. Furthermore, the mass ratio of the content of one functional group-containing component to the content of the other functional group-containing component [content of one functional group-containing component / content of the other functional group-containing component] is preferably 0.001 to 5000, more preferably 0.01 to 1000, and even more preferably 0.02 to 200.
[0266] When polymer (b) contains both a component with a carboxyl group and a component with a carboxylic anhydride group, the total content described above can be considered to appropriately determine the content of each component in the polymer containing both carboxyl and carboxylic anhydride groups. For example, in a preferred embodiment, the content can be set to the same range as when polymer (b) has two types of functional groups. However, the content of the component with a carboxyl group can be the content of one of the functional groups or the content of the other functional group.
[0267] (As a constituent component with substituents having 8 or more carbon atoms in the side chain)
[0268] Polymer (b) preferably contains one or more substituents having eight or more carbon atoms as side chains. When polymer (b) contains such substituents, the polarity (SP value) of polymer (b) is reduced, which can improve the solubility of polymer binder (B) in dispersion medium (D) and contribute to the improvement of dispersion properties.
[0269] The constituent can be any constituent that forms polymer (b), wherein substituents having 8 or more carbon atoms are introduced as side chains of polymer (b) or as part thereof. The constituent has substituents having 8 or more carbon atoms directly or via linkers in a portion of the main chain incorporated into polymer (b).
[0270] As part of the main chain of polymer (b), the structure can be appropriately selected according to the type of polymer, as described above.
[0271] Substituents having 8 or more carbon atoms are not particularly limited. For example, substituent Z described later can be considered as a group having 8 or more carbon atoms. When a constituent component is included as a side chain of a polymer chain, a substituent having 8 or more carbon atoms includes substituents having 8 or more carbon atoms in each constituent component constituting the polymer chain. However, the polymer chain as a whole is considered as one substituent rather than a substituent having 8 or more carbon atoms.
[0272] As a substituent having 8 or more carbon atoms, examples include long-chain alkyl groups having 8 or more carbon atoms, cycloalkyl groups having 8 or more carbon atoms, aryl groups having 8 or more carbon atoms, aralkyl groups having 8 or more carbon atoms, and heterocyclic groups having 8 or more carbon atoms, with long-chain alkyl groups having 8 or more carbon atoms being preferred.
[0273] The number of carbon atoms in the substituent can be 8 or more, preferably 10 or more, more preferably 12 or more. There is no particular upper limit, but it is preferably 24 or less, more preferably 20 or less, and even more preferably 16 or less. The number of carbon atoms in the substituent indicates the number of carbon atoms constituting the substituent. When the substituent also has other substituents, the number of carbon atoms constituting the other substituents is included.
[0274] There are no particular restrictions on the linking group that connects the partial structure incorporated into the main chain and the substituents with 8 or more carbon atoms. The linking group L in the aforementioned constituent components containing functional groups is not particularly limited. F The same, but particularly preferred, are -CO-O- groups or -CO-N(R) groups. N )-group (R N (As mentioned above).
[0275] The structure incorporated into the main chain, the linking group, and the substituents having 8 or more carbon atoms may each have substituents. There are no particular restrictions on such substituents; for example, groups selected from substituents Z described later can be cited, and groups other than those in functional group (a) are preferred.
[0276] As a constituent having substituents having 8 or more carbon atoms, it can be formed by appropriately combining the partial structure incorporated into the main chain, the substituents having 8 or more carbon atoms, and the linking group. For example, it is preferably a constituent represented by the following formula (1-1).
[0277] [Chemical Formula 2]
[0278]
[0279] In equation (1-1), R 1 Represents a hydrogen atom or an alkyl group (preferably 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3). As R 1 The alkyl group used may have substituents. There are no particular limitations on the substituents, and examples such as the substituent Z mentioned above are possible. Preferably, the substituents are groups other than those in functional group (a), such as halogen atoms.
[0280] R 2 This refers to a substituent group having 8 or more carbon atoms. In this invention, the substituent group includes a group consisting of the substituent itself (the substituent is directly bonded to R). 1 The carbon atoms in the above formula that are bonded. ) and the carbon atoms connected by R 2 The carbon atom and the linking group of the substituent in the above formula are bonded together, and the substituent group is formed by the substituent (the substituent is bonded to R via the linking group). 1 The carbon atoms in the above formula that are bonded.
[0281] As R 2 The substituents having 8 or more carbon atoms, and R 2 It can have connection bases, as described above. As R 2 Especially preferred are long-chain alkyl groups with 8 or more carbon atoms, such as -C(=O)-O-.
[0282] In the above equation (1-1), with R 1 The carbon atoms adjacent to the bonded carbon atoms have two hydrogen atoms, but in this invention, they may have one or two substituents. There are no particular limitations on the substituents, and examples such as substituent Z described later can be given, but groups other than those in functional group (a) are preferred.
[0283] As a constituent component having a substituent having 8 or more carbon atoms, for example, it is preferable to be a constituent component of a compound having a substituent having 8 or more carbon atoms from the (meth)acrylic acid compound (M1) described later, or a constituent component of a compound having a substituent having 8 or more carbon atoms from the other polymeric compound (M2) described later, and preferably a (meth)acrylic acid (8 or more carbon atoms) long-chain alkyl ester compound.
[0284] Specific examples of constituents having substituents having 8 or more carbon atoms include constituents in exemplary polymers described later and polymers synthesized in the examples, but the invention is not limited to these.
[0285] From the viewpoint of the dispersion characteristics of the adhesive (B), the content of the constituent components having substituents having 8 or more carbon atoms in the polymer (b) is not particularly limited, preferably 20 to 99.9% by mass, more preferably 30 to 99.5% by mass, further preferably 40 to 99% by mass, especially preferably 60 to 98% by mass, and most preferably 80 to 95% by mass.
[0286] (Other constituent components)
[0287] Polymer (b) may contain constituents other than those containing functional groups and having substituents having 8 or more carbon atoms (referred to as other constituents). There are no particular restrictions on other constituents as long as they can form polymer (b), and they can be appropriately selected according to the type of polymer (b). For example, constituents derived from compounds that do not have the aforementioned functional groups and substituents having 8 or more carbon atoms, as described later in the (meth)acrylic acid compound (M1) and other polymeric compounds (M2), can be cited.
[0288] As other constituent components, constituent components having substituents having 7 or fewer carbon atoms are preferably mentioned. This constituent component is the same as the constituent components having substituents having 7 or fewer carbon atoms, except that it has substituents replacing substituents having 8 or more carbon atoms. Specifically, constituent components derived from alkyl ester compounds with 7 or fewer carbon atoms of (meth)acrylic acid are preferred; for example, constituent components derived from methyl (meth)acrylate, ethyl (meth)acrylate, etc., are examples.
[0289] The content of other constituent components in polymer (b) is not particularly limited, and can be appropriately determined from 0 to 100% by mass, taking into account the content of the aforementioned constituent components. When polymer (b) contains other constituent components, for example, it is preferably 1 to 60% by mass, more preferably 2 to 40% by mass, and even more preferably 5 to 20% by mass.
[0290] (Components of macromonomers)
[0291] Polymer (b) preferably has a main chain composed of at least one of the above-mentioned constituent components. Furthermore, it is also preferred that the main chain of polymer (b) contains a macromolecular monomer constituent component (polymer (b) is equivalent to a grafted polymer). That is, each of the above-mentioned constituent components can be incorporated as a main chain constituent component constituting the main chain of polymer (b), or as a side chain constituent component constituting the polymer (b), such as a polymer chain constituent component.
[0292] When each component is incorporated as a side chain, such as a polymer chain component, of the polymer (b), the main chain component constituting the polymer (b) can be a component derived from a macromonomer component having a polymer chain (also called a macromonomer component). Examples of macromonomers incorporated as macromonomer components include macromonomers having polymer chains incorporated directly or via a linker into the main chain of the polymer (b). The partial structure incorporated into the main chain of the polymer (b) can be appropriately selected according to the type of polymer, as described above. There are no particular limitations on the linker; it can be the linker L in the aforementioned component containing a functional group. F Similarly, but preferably including a chain transfer agent for synthesizing the above-mentioned polymer chain, a linker containing a structural portion (residue) derived from a polymerization initiator, etc., and a linker bonded to a structural portion (glycidyl group) derived from a (meth)acrylic acid compound (M1) reacting with the above-mentioned chain transfer agent, such as a structural portion (glycidyl group) derived from a (meth)acrylic acid glycidyl ester compound. There are no particular limitations on the chain transfer agent; examples include 3-mercaptopropionic acid, mercaptoacetic acid, 2-mercaptopropionic acid, 3-mercaptoisobutyric acid, 2-mercaptoethanol, 6-mercapto-1-hexanol, 2-aminoethanethiol, and 2-aminoethanethiol hydrochloride. Examples of linkers composed of a structural portion derived from the chain transfer agent and a structural portion derived from a (meth)acrylic acid compound (M1) include -CO-O-alkylene-X-CO-(X)n-alkylene-S-yl. Here, X represents an oxygen atom or -NH-, and n is 0 or 1. More specifically, examples can be given of the linking groups in the constituent components (X) of the polymer synthesized in the embodiments. The number of atoms constituting the linking group in the macromonomer is preferably 1 to 36, more preferably 1 to 30, and even more preferably 1 to 24. The number of linking atoms in the linking group is preferably 16 or less, more preferably 12 or less, and particularly preferably 10 or less.
[0293] There are no particular limitations on the polymer chain that a macromonomer may possess. Examples of polymer chains that have functional group-containing components, substituents having 8 or more carbon atoms, or other components as polymer chain components can be given. Specifically, examples include the polymer chains of chain polymers described later. When a polymer chain contains the aforementioned functional group-containing components as polymer chain components, regardless of the presence or absence of substituents having 8 or more carbon atoms or other components, the macromonomer component is equivalent to the functional group-containing component constituting polymer (b) (the aforementioned "polymer chain-containing component"). However, even if the macromonomer component has a linker containing a functional group selected from the aforementioned functional group group (a), as long as the polymer chain does not contain the aforementioned functional group-containing component, it is designated as a "macromonomer component".
[0294] There are no particular limitations on the content of functional group-containing components, substituents having 8 or more carbon atoms, and other components in the polymer chain. However, when converted to the content in polymer (b), it is preferable to satisfy the range of the content of each component in polymer (b) described above. For example, the content of functional group-containing components incorporated into the macromonomer is preferably 1 to 100% by mass, more preferably 3 to 80% by mass, even more preferably 5 to 70% by mass, and particularly preferably 5 to 25% by mass. The content of substituents having 8 or more carbon atoms is preferably 0 to 90% by mass, in one embodiment, more preferably 1 to 70% by mass, even more preferably 5 to 50% by mass, and in another embodiment, even more preferably 70 to 90% by mass. The content of other components is preferably 0 to 50% by mass, more preferably 0 to 30% by mass, and even more preferably 0 to 20% by mass.
[0295] There is no particular limitation on the number average molecular weight of the macromonomer. From the viewpoint of maintaining excellent dispersion characteristics while making the adhesion of solid particles and the tightness with the current collector stronger, it is preferably 500 to 100,000, more preferably 1,000 to 50,000, and even more preferably 2,000 to 20,000.
[0296] The content of the macromonomer component in polymer (b) is set to satisfy the range of the contents of each of the above-mentioned components. From the viewpoint of dispersion characteristics and adsorption properties of polymer binder (B), the content of the macromonomer component alone in polymer (b) is preferably 0.1 to 70% by mass, more preferably 2 to 70% by mass, even more preferably 5 to 60% by mass, particularly preferably 8 to 50% by mass, and most preferably 10 to 40% by mass.
[0297] The following is a detailed description of the chain polymers suitable for use in this invention.
[0298] (hydrocarbon polymer)
[0299] Examples of hydrocarbon polymers include polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymers, styrene-based thermoplastic elastomers, polybutene, acrylonitrile-butadiene copolymers, or their hydrogenated (hydrogenated) polymers. There are no particular limitations on styrene-based thermoplastic elastomers or their hydrogenated derivatives; examples include styrene-ethylene-butene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymers (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers of SEBS and other block copolymers corresponding to the aforementioned block copolymers. In this invention, the preferred feature of the hydrocarbon polymer is that the polymer without unsaturated groups (e.g., 1,2-butadiene components) bonded to the main chain can suppress the formation of chemical crosslinks.
[0300] The aforementioned hydrocarbon polymer preferably contains the aforementioned constituent components containing functional groups, such as constituent components derived from polymerizable cyclic dicarboxylic anhydrides like maleic anhydride. Furthermore, it is preferable to contain constituent components having substituents having 8 or more carbon atoms.
[0301] There are no particular restrictions on the content of the constituent components in the hydrocarbon polymer. The appropriate selection can be made by considering conditions (1) to (4) and other physical properties, for example, it can be set within the range mentioned above.
[0302] (Vinyl polymer)
[0303] Examples of vinyl polymers include polymers containing 50 mol% or more of vinyl monomers other than (meth)acrylic acid compound (M1). Examples of vinyl monomers include vinyl compounds described later. Specifically, examples of vinyl polymers include polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate, or copolymers containing these.
[0304] The vinyl polymer preferably contains, in addition to components derived from ethylene monomers, the aforementioned components containing functional groups, and even more preferably, components containing substituents having 8 or more carbon atoms.
[0305] There are no particular restrictions on the content of the constituent components in the vinyl polymer, and they can be appropriately selected by considering conditions (1) to (4) and other physical properties. For example, the content of the constituent components derived from vinyl monomers in all the constituent components of the vinyl polymer is preferably the same as the content of the constituent components derived from (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer. Here, when the constituent components having substituents having 8 or more carbon atoms and the constituent components having functional groups are constituent components derived from vinyl monomers, the content of these constituent components is included in the content of constituent components derived from vinyl monomers. The content of the constituent components having substituents having 8 or more carbon atoms and the content of the constituent components having functional groups in all the constituent components of the vinyl polymer are as described above. There are no particular restrictions on the content of the constituent components derived from (meth)acrylic acid compound (M1) in the polymer as long as it is less than 50 mol%, and it is preferably 0 to 30 mol%.
[0306] ((meth)acrylic acid polymer)
[0307] As a (meth)acrylic acid polymer, a polymer obtained by copolymerizing at least one (meth)acrylic acid compound (M1) selected from (meth)acrylic acid compounds, (meth)acrylate compounds, (meth)acrylamide compounds, and (meth)acrylonitrile compounds is preferred. A polymer having at least one of the following components: a component derived from the (meth)acrylic acid compound (M1), a component having a substituent having 8 or more carbon atoms, and a component having a functional group is also preferred. Furthermore, polymers containing components derived from other polymerizable compounds (M2) are also preferred.
[0308] Examples of (meth)acrylate compounds include alkyl (meth)acrylate compounds, aryl (meth)acrylate compounds, heterocyclic (meth)acrylate compounds, and polymeric (meth)acrylate compounds, with alkyl (meth)acrylate compounds being preferred. The number of carbon atoms in the alkyl group constituting the (meth)acrylate compound is not particularly limited, and can be, for example, 1 to 24. From the viewpoint of improving dispersibility and adhesion, 3 to 20 is preferred, more preferably 4 to 16, and even more preferably 8 to 14. The number of carbon atoms in the aryl group constituting the aryl ester is not particularly limited, and can be, for example, 6 to 24, preferably 6 to 10, and more preferably 6. In (meth)acrylamide compounds, the nitrogen atom of the amide group can be substituted with an alkyl or aryl group.
[0309] There are no particular limitations on other polymerizable compounds (M2), and examples include styrene compounds, vinylnaphthalene compounds, vinyl carbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, itaconic acid dialkyl compounds, unsaturated carboxylic anhydrides, and other vinyl compounds and their fluorides. As a vinyl compound, for example, the "ethylene monomers" described in Japanese Patent Application Publication No. 2015-88486 can be cited.
[0310] (Meth)acrylic acid compounds (M1) and other polymeric compounds (M2) may have substituents. There are no particular limitations on the substituents, but groups selected from substituents Z described later are preferred.
[0311] The content of the constituent components in the (meth)acrylic acid polymer is not particularly limited, and can be appropriately selected considering conditions (1) to (4) and other physical properties. For example, the content of the constituent components derived from the (meth)acrylic acid compound (M1) among all the constituent components constituting the (meth)acrylic acid polymer is not particularly limited, and can be appropriately set in the range of 0 to 100 mol%. The upper limit can be set to 90 mol%, for example. Here, when the constituent components having substituents with 8 or more carbon atoms and the constituent components containing functional groups are constituent components derived from the (meth)acrylic acid compound (M1), the content of these constituent components is included in the content of the constituent components derived from the (meth)acrylic acid compound (M1). The content of the constituent components having substituents with 8 or more carbon atoms, the constituent components containing the functional groups and other constituent components among all the constituent components constituting the (meth)acrylic acid polymer are as described above. The content of other polymeric compounds (M2) in all the constituent components of the (meth)acrylic acid polymer is not particularly limited, for example, it can be set to less than 50 mol%, preferably 1 to 30 mol%, more preferably 1 to 20 mol%, and even more preferably 2.5 to 20 mol%.
[0312] The (meth)acrylic acid compound (M1) and other polymerizable compounds (M2) used as constituent components of (meth)acrylic acid polymers and vinyl polymers are preferably compounds represented by the following formula (b-1). This compound is preferably different from compounds that introduce constituent components having substituents having 8 or more carbon atoms or compounds that introduce constituent components containing the aforementioned functional groups.
[0313] [Chemical Formula 3]
[0314]
[0315] In the formula, R 1The group represents a hydrogen atom, hydroxyl group, cyano group, halogen atom, alkyl group (preferably with 1 to 24 carbon atoms, more preferably 1 to 12, especially preferably 1 to 6), alkenyl group (preferably with 2 to 24 carbon atoms, more preferably 2 to 12, especially preferably 2 to 6), alkynyl group (preferably with 2 to 24 carbon atoms, more preferably 2 to 12, especially preferably 2 to 6), or aryl group (preferably with 6 to 22 carbon atoms, more preferably 6 to 14). Among these, hydrogen atoms or alkyl groups are preferred, and hydrogen atoms or methyl groups are even more preferred.
[0316] R 2 Represents a hydrogen atom or substituent. It can be represented as R. 2 The substituents are not particularly limited, and examples include alkyl (which may be branched, but preferably straight), alkenyl (preferably with 2 to 12 carbon atoms, more preferably 2 to 6, especially preferably 2 or 3), aryl (preferably with 6 to 22 carbon atoms, more preferably 6 to 14), aralkyl (preferably with 7 to 23 carbon atoms, more preferably 7 to 15), and cyano.
[0317] The number of carbon atoms in the alkyl group has the same meaning as the number of carbon atoms in the alkyl group constituting the above-mentioned alkyl methacrylate compound, but is preferably a long-chain alkyl ester with 8 or more carbon atoms or an alkyl ester with 7 or fewer carbon atoms.
[0318] L 1 The linking group is not particularly limited; for example, a linking group in a constituent having substituents having 8 or more carbon atoms as described above can be cited. The linking group can have any substituents. The number of atoms constituting the linking group and the number of linking atoms are as described above. As an arbitrary substituent, the substituent Z described later can be cited, for example, alkyl or halogen atoms, etc.
[0319] n is 0 or 1, preferably 1. Where, -(L 1 ) n -R 2 When representing a single substituent (e.g., alkyl), set n to 0 and R to... 2 Set as a substituent (alkyl).
[0320] In the above formula (b-1), the carbon atom that forms the polymerizable group and is not bonded to R 1 The carbon atom is represented as an unsubstituted carbon atom (H₂C=), but it may have substituents. There are no particular restrictions on the substituents, but examples such as R can be used. 1 The above-mentioned groups.
[0321] Furthermore, substituents such as alkyl, aryl, alkylene, and aryl groups may be present without impairing the effects of the present invention. There are no particular limitations on the substituents; for example, groups selected from substituent Z described later can be cited, specifically, halogen atoms, etc.
[0322] As the aforementioned (meth)acrylic acid compound (M1), compounds represented by the following formulas (b-2) or (b-3) are also preferred. This compound is preferably different from compounds that introduce substituents having 8 or more carbon atoms or compounds that introduce substituents having the aforementioned functional groups.
[0323] [Chemical Formula 4]
[0324]
[0325] R 1 The meanings of and n are the same as those in the above formula (b-1).
[0326] R 3 With R 2 The meanings are the same.
[0327] L 2 As a connecting base, the above-mentioned L can be preferentially applied. 1 The records.
[0328] L 3 As a connecting base, the above-mentioned L can be preferentially applied. 1 The preferred form is an alkylene group having 1 to 6 carbon atoms (preferably 1 to 3).
[0329] m is an integer from 1 to 200, preferably an integer from 1 to 100, and more preferably an integer from 1 to 50.
[0330] In the above formulas (b-1) to (b-3), the carbon atoms that form polymeric groups and are not bonded to R 1 The carbon atom is represented as an unsubstituted carbon atom (H₂C=), but it may have substituents. There are no particular restrictions on the substituents, but examples such as R can be used. 1 The above-mentioned groups.
[0331] Furthermore, in formulas (b-1) to (b-3), groups employing substituents such as alkyl, aryl, alkylene, and arylene may have substituents to a extent that does not impair the effects of the present invention. Substituents may be any substituent other than those selected from the functional group (a), for example, groups selected from substituent Z described later; specifically, halogen atoms, etc., may be included.
[0332] As described above, polymer (b) is preferably a random polymer or a block polymer. When polymer (b) is a block polymer, there is no particular limitation as long as the number of blocks (segments) forming the block polymer is 2 or more, and it can be set to 2 to 5, preferably 2 or 3.
[0333] As block polymers, when the different blocks forming the block polymer are designated as A, B, and C, examples include AB type (a polymer in which one block A and one block B are bonded to form one polymer chain (main chain)), ABA type (a polymer in which two blocks A are bonded to both ends of one block B to form one polymer chain (main chain)), and ABC type (a polymer in which one block A, one block B, and one block C are sequentially bonded to form one polymer chain (main chain)). Among these, the ABA type is preferred.
[0334] Here, blocks A, B, and C can each be a block composed of one type of constituent element, or a block with two or more constituent elements. When there are two or more constituent elements, there is no particular limitation on the bonding mode (configuration) of each constituent element, and it can be any of random bonding, alternating bonding, block bonding, etc., with random bonding being preferred.
[0335] In polymer (b), the constituent components constituting block A are not particularly limited, but it is preferable to contain the other constituent components mentioned above, and more preferably to contain constituent components derived from alkyl ester compounds with 7 or fewer carbon atoms derived from (meth)acrylic acid. The constituent components constituting block B are not particularly limited, but it is preferable to contain the constituent components containing functional groups mentioned above and constituent components having substituents with 8 or more carbon atoms. Polymer (b) having such blocks can improve dispersion properties.
[0336] The content of each block in the block polymer is not particularly limited and can be appropriately set considering conditions (1) to (4) and other physical properties. For example, the content of block A containing the above-mentioned constituent components in polymer (b) is preferably 5 to 60% by mass, more preferably 8 to 50% by mass, and even more preferably 10 to 40% by mass. The content of block B containing the above-mentioned constituent components with functional groups and the constituent components having substituents with 8 or more carbon atoms in polymer (b) is preferably 40 to 95% by mass, more preferably 50 to 92% by mass, and even more preferably 60 to 90% by mass.
[0337] The content of each component in the block polymer is not particularly limited, and the above content is set in all the components of polymer (b) according to the type of polymer (b).
[0338] The end groups of polymer (b) are introduced with appropriate groups, such as hydrogen atoms, chain transfer agent residues, initiator residues, etc., through polymerization methods, polymerization stopping methods, etc.
[0339] The chain polymer (constituent components and raw material compounds) may have substituents. There are no particular limitations on the substituents, but groups selected from the substituents Z below are preferred, and groups other than those included in the functional group (a) above are preferred.
[0340] -Substituent Z-
[0341] Examples of alkyl groups include alkyl groups (preferably alkyl groups with 1 to 20 carbon atoms, such as methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups with 2 to 20 carbon atoms, such as vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups with 2 to 20 carbon atoms, such as ethynyl, butyrynyl, phenylethynyl, etc.), and cycloalkyl groups (preferably cycloalkyl groups with 3 to 20 carbon atoms, such as cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc.). When the alkyl group is used in this invention, it is generally... The term usually indicates the presence of cycloalkyl groups, but is described separately here. Aryl groups (preferably aryl groups with 6 to 26 carbon atoms, such as phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl groups (preferably aralkyl groups with 7 to 23 carbon atoms, such as benzyl, phenethyl, etc.), and heterocyclic groups (preferably heterocyclic groups with 2 to 20 carbon atoms, more preferably heterocyclic groups with a 5 or 6-membered ring having at least one oxygen atom, sulfur atom, and nitrogen atom). Heterocyclic groups include aromatic heterocyclic groups and aliphatic heterocyclic groups. For example, tetrahydropyranyl, tetrahydrofuranyl, 2-pyridyl, etc. 4-pyridinyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidone, etc.), alkoxy groups (preferably alkoxy groups with 1 to 20 carbon atoms, such as methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy groups (preferably aryloxy groups with 6 to 26 carbon atoms, such as phenoxy, 1-naphthoxy, 3-methylphenoxy, 4-methoxyphenoxy, etc.), heterocyclic oxy groups (groups with -O- groups bonded to the above heterocyclic groups), alkoxycarbonyl groups (preferably alkoxycarbonyl groups with 2 to 20 carbon atoms, such as ethoxycarbonyl, 2-ethylhexyloxycarbonyl, etc.). Dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl with 6 to 26 carbon atoms, such as phenoxycarbonyl, 1-naphthoxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), heterocyclic oxycarbonyl (a group with -O-CO- group bonded to the above heterocyclic group), amino (preferably amino, alkylamino, arylamino containing 0 to 20 carbon atoms, such as amino(-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, aniline, etc.), aminosulfonyl (preferably aminosulfonyl with 0 to 20 carbon atoms, such as N,N-dimethylaminosulfonyl, N-phenylaminosulfonyl, etc.), acyl groups (including alkyl carbonyl, alkenyl carbonyl, alkynyl carbonyl, aryl carbonyl, heterocyclic carbonyl, preferably acyl groups with 1 to 20 carbon atoms, such as acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryl, methacryl, crotonyl, benzoyl, naphthoyl, nicotinyl, etc.), acyloxy groups (including alkyl carbonyloxy, alkenyl carbonyloxy, alkynyl carbonyloxy, heterocyclic carbonyloxy, preferably acyloxy groups with 1 to 20 carbon atoms, such as acetyloxy, propionyloxy, butyryloxy, octanoyloxy, hexadecanoyl, etc.), Acryloyloxy, methacryloyloxy, crotonyloxy, nicotinoxy, etc.), aromatic acryloyloxy (preferably aromatic acryloyloxy with 7 to 23 carbon atoms, such as benzoyloxy, naphthyloxy, etc.), carbamoyl (preferably carbamoyl with 1 to 20 carbon atoms, such as N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), amide (preferably amide with 1 to 20 carbon atoms, such as acetamido, benzoylamino, etc.), alkylthio (preferably alkylthio with 1 to 20 carbon atoms, such as methylthio, ethylthio, isopropylthio, benzylthio, etc.) Arylthioyl (preferably arylthioyl with 6 to 26 carbon atoms, such as phenylthioyl, 1-naphthioyl, 3-methylphenylthioyl, 4-methoxyphenylthioyl, etc.), heterocyclic thioyl (a group with -S- group bonded to the above heterocyclic group), alkylsulfonyl (preferably alkylsulfonyl with 1 to 20 carbon atoms, such as methylsulfonyl, ethylsulfonyl, etc.), arylsulfonyl (preferably arylsulfonyl with 6 to 22 carbon atoms, such as benzenesulfonyl, etc.), alkylsilyl (preferably alkylsilyl with 1 to 20 carbon atoms, such as monomethylsilyl, dimethylsilyl, trimethylsilyl, etc.). alkylsilyl, triethylsilyl, etc.), arylsilyl (preferably arylsilyl with 6 to 42 carbon atoms, such as triphenylsilyl), alkoxysilyl (preferably alkoxysilyl with 1 to 20 carbon atoms, such as monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably aryloxysilyl with 6 to 42 carbon atoms, such as triphenoxysilyl), phosphoryl (preferably phosphoric acid with 0 to 20 carbon atoms, such as -OP(=O)(R, P )2) Phosphonyl group (preferably a phosphonyl group with 0 to 20 carbon atoms, for example, -P(=O)(R P )2) Oxyphosphin group (preferably oxyphosphin group with 0 to 20 carbon atoms, for example, -P(R P 2) Phosphonic acid group (preferably a phosphonic acid group with 0 to 20 carbon atoms, for example, -PO(OR) P 2) Sulfonate (sulfonic acid group), carboxyl group, hydroxyl group, thioalkyl group, cyano group, halogen atom (e.g., fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). R PIt is a hydrogen atom or a substituent (preferably a group selected from substituent Z).
[0342] Furthermore, each of the groups listed in these substituents Z can be further replaced by the aforementioned substituents Z.
[0343] The aforementioned alkyl, alkylene, alkenyl, alkenylene, ynyl and / or ynylene groups can be cyclic or chain-like, and can be straight-chain or branched.
[0344] Block polymers can be synthesized by selecting and polymerizing feedstock compounds using known methods. Furthermore, there are no particular restrictions on the synthesis methods of block polymers; well-known methods can be employed. For example, living radical polymerization can be used. Examples of living radical polymerization methods include atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer polymerization (RAFT), and nitride-mediated polymerization (NMP).
[0345] There are no particular limitations on the methods for incorporating functional groups. Examples include copolymerizing compounds having functional groups selected from group (a), using polymerization initiators or chain transfer agents having (generating) the aforementioned functional groups, utilizing polymer reactions, reactions of olefins in double bonds, olefin-thiols reactions, or ATRP (Atom Transfer Radical Polymerization) polymerization using copper catalysts. Furthermore, functional groups can be introduced by using functional groups present in the polymer's main chain, side chains, or ends as reaction sites. For example, by using compounds having functional groups, functional groups selected from group (a) can be introduced through various reactions with carboxylic anhydride groups in the polymer chain.
[0346] Specific examples of polymers constituting polymeric adhesives include polymers C-1 to C-14 shown below and the polymers synthesized in the examples, but the present invention is not limited to these. Furthermore, in the chemical formulas of the following polymers, when blocks are designated as A and B, "A-block-B" indicates a nomenclature based on the copolymer's raw material base, and "-block-" indicates a block polymer composed of blocks of component A and blocks of component B. In the following chemical formulas, the numerical value to the right of each component indicates its content (mass %) in the polymer, and Me represents methyl.
[0347] [Chemical Formula 5]
[0348]
[0349] The polymer binder (B) contained in the electrode composition of the present invention may be one type or two or more types.
[0350] From the viewpoints of dispersion characteristics, solid particle cohesion, and cycling characteristics, the content of polymer binder (B) in the electrode composition is preferably 0.1 to 10% by mass of 100% of the solid component, more preferably 0.3 to 8% by mass, even more preferably 0.5 to 7% by mass, and particularly preferably 0.5 to 3% by mass.
[0351] In this invention, the mass ratio of the total mass (total amount) of inorganic solid electrolyte and active material to the total content of polymer binder in 100% by mass of solid component [(mass of inorganic solid electrolyte + mass of active material) / (total mass of polymer binder)] is preferably in the range of 1,000 to 1. Furthermore, this ratio is more preferably 500 to 2, and even more preferably 100 to 10.
[0352] (Other polymer adhesives)
[0353] The electrode composition of the present invention may contain one or more polymer binders other than the polymer binder (B) described above, such as polymer binders that do not satisfy any one of the conditions (1) to (4) above (also referred to as other polymer binders). Examples of other polymer binders include, for example, polymer binders that are insoluble in the dispersion medium and exist (dispersed) in the electrode composition in particulate form (particulate binders), and the adsorption rate relative to the conductive additive [A] CA The polymer binder contains more than 50% polymer binders (high-adsorption binders), etc. The particle size of this particulate binder is preferably 1 to 1,000 nm. The particle size can be measured in the same manner as the particle size of the aforementioned inorganic solid electrolyte. Various polymer binders used in the manufacture of all-solid-state secondary batteries can be used without particular limitation as other polymer binders.
[0354] There are no particular limitations on the content of other polymer binders in the electrode composition, but for example, it is preferred to be 0.01 to 4% by mass in 100% by mass of the solids component.
[0355] <Dispersion Medium (D)>
[0356] The electrode composition of the present invention contains a dispersion medium (D) that disperses or dissolves the above-mentioned components.
[0357] As such a dispersion medium, any organic compound that appears as a liquid in the environment of use can be used, such as various organic solvents, specifically alcohols, ethers, amides, amines, ketones, aromatics, aliphatic compounds, nitriles, esters, etc.
[0358] The dispersion medium can be either a nonpolar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium). From the viewpoint of exhibiting excellent dispersion characteristics, a nonpolar dispersion medium is preferred. A nonpolar dispersion medium generally refers to a medium with low affinity for water; however, in this invention, examples include ester compounds, ketone compounds, ether compounds, aromatic compounds, and aliphatic compounds.
[0359] Examples of alcohol compounds include, for example, methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0360] Examples of ether compounds include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl ether, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxanes (including 1,2-, 1,3- and 1,4- isomers, etc.)).
[0361] Examples of amide compounds include, for example, N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, hexamethylphosphoric triamide, etc.
[0362] Examples of amine compounds include triethylamine, diisopropylethylamine, and tri-n-butylamine.
[0363] Examples of ketone compounds include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutylpropyl ketone, sec-butylpropyl ketone, pentylpropyl ketone, butylpropyl ketone, etc.
[0364] Examples of aromatic compounds include, for example, benzene, toluene, xylene, and perfluorotoluene.
[0365] Examples of aliphatic compounds include hexane, heptane, octane, nonane, decane, dodecane, cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, cyclooctane, decahydronaphthalene, paraffin wax, gasoline, naphtha, kerosene, and light oil.
[0366] Examples of nitrile compounds include acetonitrile, propionitrile, and isobutyronitrile.
[0367] Examples of ester compounds include, for example, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, pentyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl neovalerate, isopropyl neovalerate, butyl neovalerate, isobutyl neovalerate, etc.
[0368] In this invention, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ester compounds, ketone compounds, or ether compounds are more preferred.
[0369] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, even more preferably 6 to 15, and especially preferably 7 to 12.
[0370] From the perspective of dispersion characteristics, and from the perspective of preventing the deterioration (decomposition) of sulfide-based inorganic solid electrolytes when used as inorganic solid electrolytes, the dispersion medium is preferably low polarity (low-polarity dispersion medium). For example, SP value (unit: MPa) 1 / 2 The value can typically be set in the range of 15 to 27, preferably 17 to 22, more preferably 17.5 to 21, and even more preferably 18 to 20.
[0371] The difference (absolute value, unit: MPa) between the SP value of the polymer adhesive (B) and the SP value of the dispersion medium (D). 1 / 2 There are no particular limitations, but from the viewpoint of further improving dispersion characteristics, a value of 3.0 or less is preferred, more preferably 0 to 2.5, even more preferably 0 to 2.0, and particularly preferably 0 to 1.7. When the electrode composition contains multiple polymer binders (B), the difference (absolute value) of the SP values is preferably the smallest value (absolute value) included in the above range.
[0372] The SP value of the dispersion medium is set to be the SP value calculated by the Hoy method above, converted to MPa. 1 / 2 The SP value is obtained as follows. When the electrode composition contains two or more dispersion media, the SP value of the dispersion media (D) refers to the SP value of the entire dispersion media, and is set as the sum of the products of the SP values of each dispersion media and their mass fractions. Specifically, the SP values of each dispersion media are used instead of the SP values of the constituent components, and the calculation is performed in the same way as the calculation method for the SP values of the polymers described above.
[0373] The following shows the SP values (units omitted) for the dispersion media. Additionally, in the following compound names, unless otherwise specified, alkyl refers to n-alkyl.
[0374] MIBK (18.4), diisopropyl ether (16.8), dibutyl ether (17.9), diisobutyl ketone (17.9), DIBK (17.9), butyl butyrate (18.6), butyl acetate (18.9), toluene (18.5), xylene (a mixture of xylene isomers with a molar ratio of ortho:para:meta = 1:5:2) (18.7), octane (16.9), ethylcyclohexane (17.1), cyclooctane (18.8), isobutyl ethyl ether (15.3), N-methylpyrrolidone (NMP, SP value: 25.4), perfluorotoluene (SP value: 13.4)
[0375] There is no particular limitation on the boiling point of the dispersion medium at atmospheric pressure (1 atmosphere), but it is preferably 90°C or higher, more preferably 120°C or higher. The upper limit is preferably 230°C or lower, more preferably 200°C or lower.
[0376] The electrode composition of the present invention may contain one or more dispersion media. Examples of containing two or more dispersion media include mixed xylenes (a mixture of o-xylene, p-xylene, m-xylene, and ethylbenzene).
[0377] There is no particular limitation on the content of the dispersion medium in the electrode composition; it can be set within the range that satisfies the above-mentioned concentration of solid components.
[0378] <Lithium Salts>
[0379] The electrode composition of the present invention may also contain a lithium salt (supporting electrolyte). As the lithium salt, a lithium salt commonly used in this type of product is preferred, without particular limitation; for example, the lithium salt described in paragraphs 0082 to 0085 of Japanese Patent Application Publication No. 2015-088486 is preferred. When the electrode composition of the present invention contains a lithium salt, the content of the lithium salt relative to 100 parts by weight of the inorganic solid electrolyte is preferably 0.1 parts by weight or more, more preferably 5 parts by weight or more. As an upper limit, it is preferably 50 parts by weight or less, more preferably 20 parts by weight or less.
[0380] <Dispersant>
[0381] In the electrode composition of the present invention, since the aforementioned polymer binder (B) also functions as a dispersant, it is possible to omit any dispersant other than the polymer binder (B). When the electrode composition contains a dispersant other than the polymer binder (B), a dispersant typically used in all-solid-state secondary batteries can be appropriately selected as the dispersant. Generally, compounds suitable for particle adsorption, steric hindrance, and / or electrostatic repulsion are appropriately used.
[0382] <Other Additives>
[0383] The electrode composition of the present invention can appropriately contain ionic liquids, thickeners, crosslinking agents (substances that undergo crosslinking reactions via free radical polymerization, condensation polymerization, or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals through heat or light, etc.), defoamers, homogenizers, dehydrating agents, antioxidants, etc., as other components besides those mentioned above. The ionic liquid is a liquid contained to further improve ionic conductivity, and known liquids can be used without particular limitation. Furthermore, commonly used binders, etc., can be included.
[0384] (Preparation of electrode composition)
[0385] The electrode composition of the present invention can be prepared by conventional methods. Specifically, it is prepared, for example, by mixing an inorganic solid electrolyte (SE), an active material (AC), a conductive additive (CA), a polymer binder (B), and a dispersion medium (D), as well as a suitable lithium salt and any other components, using various commonly used mixers, as a mixture, preferably as a slurry.
[0386] There are no particular restrictions on the mixing method; any known mixers such as ball mills, bead mills, planetary mixers, scraper mixers, roller mills, kneaders, disc pulverizers, rotation-revolution mixers, and narrow-gap dispersers can be used.
[0387] There are no particular restrictions on the mixing conditions. For example, all the above components can be mixed at once, or they can be mixed sequentially. As mixing conditions, for example, the mixing temperature can be set to 15–40°C. Furthermore, the rotation speed of the rotary-revolutionary mixer, etc., can be set to 200–3,000 rpm. As the mixing atmosphere, any atmosphere can be used, such as atmospheric pressure, dry air (dew point below -20°C), or an inert gas (e.g., argon, helium, nitrogen). Since inorganic solid electrolytes readily react with moisture, mixing under dry air or an inert gas is preferred.
[0388] Electrode sheets for all-solid-state rechargeable batteries
[0389] The electrode sheet for all-solid-state secondary batteries of the present invention (sometimes simply referred to as electrode sheet) is a sheet-shaped molded body capable of forming active material or electrode (a laminate of active material layer and current collector) for all-solid-state secondary batteries, and includes various forms depending on its application.
[0390] The electrode sheet of the present invention has an active material layer composed of the electrode composition of the present invention described above. The active material layer is formed from components derived from the electrode composition (except for the dispersion medium (D)), typically solid particles (inorganic solid electrolyte (SE), active material (AC), and conductive additive (CA)) and polymer binder (B) are bonded together in a mixed state.
[0391] In this invention, the conductive additive (CA) present in the active material layer can exist in the form of individual particles or in the form of aggregates. In either case, it is preferred that the conductive additive (CA) has an average particle size of 10 μm or less. In this embodiment, from the viewpoint of fully constructing electronic conduction pathways (further reducing battery resistance) and further improving cycle characteristics, the average particle size of the conductive additive (CA) present in the active material layer is more preferably less than 1.0 μm, more preferably 0.5 μm or less, and particularly preferably 0.4 μm or less. There is no particular limitation on the lower limit of this average particle size, for example, practically 0.05 μm, preferably 0.06 μm or more, and more preferably 0.08 μm or more. In another preferred embodiment, the average particle size of the conductive additive (CA) is the same as in condition (4) above.
[0392] The average particle size of the conductive additive (CA) present in the active material layer is determined by the arithmetic mean of the area equivalent diameters of individual particles or aggregates of the conductive additive (CA) in an SEM image obtained, for example, by observing an arbitrary cross-section of the active material layer using a scanning electron microscope (SEM). Specifically, it is set to a value obtained by the determination method described in the examples below.
[0393] In this invention, the active material layer preferably has an electronic conductivity of 10 mS / cm or higher. When an active material layer with an electronic conductivity of 10 mS / cm or higher is incorporated into an all-solid-state secondary battery, the battery resistance can be reduced. From the viewpoint of further reducing battery resistance, the electronic conductivity of the active material layer is more preferably 20 mS / cm or higher, more preferably 30 mS / cm or higher, and particularly preferably 40 mS / cm or higher. There is no particular upper limit to this electronic conductivity; for example, it can be set to 1,000 mS / cm, preferably 500 mS / cm or less, and more preferably 100 mS / cm or less.
[0394] The electronic conductivity of the active material layer is set as a value determined by the measurement method described in the examples below.
[0395] The electrode sheet of the present invention can be any electrode sheet having an active material layer composed of the electrode composition of the present invention described above. It can be a sheet in which the active material layer is formed on a substrate (current collector), or it can be a sheet formed of an active material layer without a substrate. The electrode sheet is generally a sheet having a substrate (current collector) and an active material layer, but it also includes forms having a substrate (current collector), an active material layer and a solid electrolyte layer in sequence, as well as forms having a substrate (current collector), an active material layer, a solid electrolyte layer and an active material layer in sequence.
[0396] Furthermore, the electrode sheet may have other layers besides those mentioned above. Examples of other layers include protective layers (release sheets) and coatings.
[0397] As for the substrate, there are no particular limitations as long as it is a substrate capable of supporting the active material layer. Examples include the materials described in the current collector section, organic materials, inorganic materials, and sheet-like materials (plate-like bodies). Examples of organic materials include various polymers, specifically polyethylene terephthalate, polypropylene, polyethylene, and cellulose. Examples of inorganic materials include, for example, glass and ceramics.
[0398] At least one of the active material layers of the electrode sheet is formed from the electrode composition of the present invention. The content of each component in the active material layer formed from the electrode composition of the present invention is not particularly limited, but preferably has the same meaning as the content of each component in the solid components of the electrode composition of the present invention. The layer thickness of each layer constituting the electrode sheet of the present invention is the same as the layer thickness described later in the description of all-solid-state secondary batteries.
[0399] In this invention, each layer constituting the sheet for all-solid-state secondary batteries can be a single-layer structure or a multi-layer structure.
[0400] In addition, when the solid electrolyte layer or active material layer is not formed by the electrode composition of the present invention, it is formed by a conventional constituent layer forming material.
[0401] In the electrode sheet of the present invention, the active material layer is formed by the electrode composition of the present invention, and has an active material layer that suppresses the increase of the interfacial resistance of solid particles while binding solid particles containing a conductive additive (CA) with an average particle size of 10 μm or less, preferably less than 1.0 μm. Therefore, the electrode sheet for all-solid-state secondary batteries of the present invention, when used as the active material layer of an all-solid-state secondary battery, enables the realization of an all-solid-state secondary battery exhibiting low resistance and excellent cycle characteristics. Furthermore, in the electrode sheet for all-solid-state secondary batteries where the active material layer is formed on the current collector, the active material layer can be firmly and tightly bonded to the current collector. Thus, the electrode sheet for all-solid-state secondary batteries of the present invention is suitable for use as the active material layer for forming an all-solid-state secondary battery, and is preferably a sheet-like component for forming electrodes (assembled as active material layers or electrodes).
[0402] [Manufacturing method of electrode sheets for all-solid-state secondary batteries]
[0403] The manufacturing method of the electrode sheet for all-solid-state secondary batteries of the present invention is not particularly limited, and it can be manufactured by forming an active material layer using the electrode composition of the present invention. For example, a method can be described as forming a film (coating and drying) of the electrode composition of the present invention on the surface of a substrate such as a current collector (which may be via another layer) to form a layer (coating and drying layer) composed of the electrode composition. Thus, it is possible to manufacture an electrode sheet for all-solid-state secondary batteries having a substrate or a coating and drying layer. Here, the coating and drying layer refers to a layer formed by coating the electrode composition of the present invention and drying the dispersion medium (i.e., a layer formed using the electrode composition of the present invention and composed of a composition from which the dispersion medium is removed from the electrode composition of the present invention). The dispersion medium may remain in both the active material layer and the coating and drying layer, provided it does not impair the effects of the present invention; the residual amount, for example, can be set to 3% by mass or less in the coating and drying layer.
[0404] In the manufacturing method of the electrode sheet for all-solid-state secondary battery of the present invention, each step such as coating and drying will be described in the following manufacturing method of all-solid-state secondary battery.
[0405] In this way, it is possible to manufacture electrode sheets for all-solid-state secondary batteries that have an active material layer consisting of a coated and dried layer, or an active material layer formed by appropriately pressurizing the coated and dried layer. The pressurization conditions, etc., will be explained in the manufacturing method of all-solid-state secondary batteries described later.
[0406] Furthermore, in the manufacturing method of the electrode sheet for all-solid-state secondary batteries of the present invention, it is also possible to peel off the substrate, protective layer (especially the sheet), etc.
[0407] [All-solid-state rechargeable battery]
[0408] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The all-solid-state secondary battery of the present invention is only required to have a structure with a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer; other structures are not particularly limited, for example, known structures related to all-solid-state secondary batteries can be used. In a preferred all-solid-state secondary battery, a positive electrode current collector is stacked on the surface of the positive electrode active material layer opposite to the solid electrolyte layer to form a positive electrode, and a negative electrode current collector is stacked on the surface of the negative electrode active material layer opposite to the solid electrolyte layer to form a negative electrode. In the present invention, each constituent layer (including the current collector, etc.) constituting the all-solid-state secondary battery can be a single-layer structure or a multi-layer structure.
[0409] In the all-solid-state secondary battery of the present invention, at least one of the negative electrode active material layer and the positive electrode active material layer is formed by the electrode composition of the present invention, and at least the positive electrode active material layer is formed by the electrode composition of the present invention. Furthermore, it is also a preferred embodiment that both the negative electrode active material layer and the positive electrode active material layer are formed by the electrode composition of the present invention. Moreover, for either the negative electrode (a stack of negative electrode current collectors) or the positive electrode (a stack of positive electrode current collectors), it is preferred that the positive electrode is formed by the electrode sheet for all-solid-state secondary batteries of the present invention, and it is also a preferred embodiment that both are formed by the electrode sheet for all-solid-state secondary batteries of the present invention.
[0410] Regarding the types and amounts of the components contained therein, the active material layer formed by the electrode composition of the present invention is preferably the same as that in the solid components of the electrode composition of the present invention.
[0411] In addition, when the active material layer is not formed by the electrode composition of the present invention, the active material layer and the solid electrolyte layer can be made using known materials.
[0412] <Positive electrode active material layer and negative electrode active material layer>
[0413] There are no particular limitations on the thickness of each of the negative electrode active material layer and the positive electrode active material layer. Considering the size of a typical all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.
[0414] The active material layer having the above-mentioned thickness can be a single layer (one-time coating of the electrode composition) or a multilayer (multiple coatings of the electrode composition). However, from the perspective of reducing resistance and increasing productivity, it is preferable to form a single layer of active material with a large layer thickness using the electrode composition of the present invention, which can be thickened by high concentration. Preferably, the layer thickness of the active material capable of forming a thick single layer of the electrode composition of the present invention can be set to, for example, 70 μm or more, and furthermore, 100 μm or more.
[0415] When the negative electrode active material layer or the positive electrode active material layer is formed by the electrode composition of the present invention, each active material layer is the same as the active material layer in the electrode sheet for all-solid-state secondary batteries of the present invention.
[0416] <Solid Electrolyte Layer>
[0417] The solid electrolyte layer is formed using a known material capable of forming a solid electrolyte layer for an all-solid-state secondary battery, and is the same as the solid electrolyte in an all-solid-state secondary battery. Its thickness is not particularly limited, but is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm.
[0418] <Current Collector>
[0419] The positive electrode active material layer and the negative electrode active material layer preferably each have a current collector on the side opposite to the solid electrolyte layer. Such positive electrode current collectors and negative electrode current collectors are preferably electron conductors.
[0420] In this invention, either the positive current collector or the negative current collector, or both together, are sometimes referred to simply as a current collector.
[0421] In addition to aluminum, aluminum alloys, stainless steel, nickel, and titanium, materials in which carbon, nickel, titanium, or silver (materials forming thin films) are treated on the surface of aluminum or stainless steel are preferred as the material forming the positive current collector. Among these, aluminum and aluminum alloys are more preferred.
[0422] In addition to aluminum, copper, copper alloys, stainless steel, nickel, and titanium, materials that have been treated with carbon, nickel, titanium, or silver on the surface of aluminum, copper, copper alloys, or stainless steel are preferred as materials for forming the negative current collector. More preferably, aluminum, copper, copper alloys, and stainless steel are preferred.
[0423] Current collectors are typically in the form of a membrane, but can also be made of mesh, perforated material, lath, porous material, foam, or fiber assembly.
[0424] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. Furthermore, it is also preferable to have irregularities on the surface of the current collector through surface treatment.
[0425] <Other Structures>
[0426] In this invention, functional layers or components may be appropriately inserted or disposed between or on the outside of the layers of the negative electrode current collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode current collector.
[0427] <Frame>
[0428] The all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the above-described structural state depending on the application, but in order to make it into a dry cell form, it is preferable to further enclose it in a suitable casing. The casing can be a metallic casing or a resin (plastic) casing. When using a metallic casing, for example, a casing made of aluminum alloy or stainless steel can be cited. Preferably, the metallic casing is divided into a positive electrode side casing and a negative electrode side casing, which are electrically connected to the positive electrode current collector and the negative electrode current collector, respectively. Preferably, the positive electrode side casing and the negative electrode side casing are joined together as one piece with a short-circuit prevention gasket.
[0429] <Preferred Implementation Method of All-Solid-State Secondary Battery>
[0430] The following is for reference. Figure 1 The preferred embodiments of the present invention will be described, but the present invention is not limited thereto.
[0431] Figure 1 This is a schematic cross-sectional view illustrating a preferred embodiment of the all-solid-state secondary battery (lithium-ion secondary battery) of the present invention. Viewed from the negative electrode side, the all-solid-state secondary battery 10 of this embodiment sequentially comprises a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5. Each layer is in contact with the others and has an adjacent structure. By employing such a structure, electrons (electrons) are supplied to the negative electrode side during charging. - ), and accumulate lithium ions (Li) here. + On the other hand, during discharge, lithium ions (Li) accumulated at the negative electrode... + The electrons return to the positive side and supply electrons to the working part 6. In the illustrated example, a light bulb is used as a model in the working part 6, and the bulb is lit by discharging.
[0432] In having Figure 1 When the layered solid-state secondary battery shown is placed in a 2032-type button cell, the solid-state secondary battery is sometimes referred to as a laminate for solid-state secondary batteries. The battery made by placing the laminate for solid-state secondary batteries in a 2032-type button cell is called a (button-type) solid-state secondary battery.
[0433] (Solid electrolyte layer)
[0434] The solid electrolyte layer can use materials that have been used in conventional all-solid-state secondary batteries without particular restrictions. This solid electrolyte layer contains an inorganic solid electrolyte with conductivity ions of metals belonging to Group 1 or Group 2 of the periodic table, and appropriate of the aforementioned components, but typically does not contain active materials.
[0435] (Positive electrode active material layer and negative electrode active material layer)
[0436] In the all-solid-state secondary battery 10, both the positive electrode active material layer and the negative electrode active material layer are formed from the electrode composition of the present invention. Preferably, the positive electrode, which is formed by stacking the positive electrode active material layer and the positive electrode current collector, and the negative electrode, which is formed by stacking the negative electrode active material layer and the negative electrode current collector, are formed from the electrode sheet of the present invention using the current collector as a substrate.
[0437] The positive electrode active material layer contains an inorganic solid electrolyte (SE) with conductivity of ions belonging to Group 1 or Group 2 of the periodic table, a positive electrode active material, a polymer binder (B), a conductive additive (CA), and any of the above-mentioned components within the scope that does not impair the effects of the present invention.
[0438] The negative electrode active material layer contains an inorganic solid electrolyte (SE) with conductivity of ions belonging to Group 1 or Group 2 of the periodic table, a negative electrode active material, a polymer binder (B), a conductive additive (CA), and any of the above-mentioned components within the range that does not impair the effects of the present invention. In the all-solid-state secondary battery 10, the negative electrode active material layer can be a lithium metal layer. Examples of lithium metal layers include layers formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited films. The thickness of the lithium metal layer is independent of the aforementioned thickness of the negative electrode active material layer, and for example, can be set to 1 to 500 μm.
[0439] The components contained in the positive electrode active material layer 4, the solid electrolyte layer 3, and the negative electrode active material layer 2, especially the inorganic solid electrolyte, conductive additives, and polymer binders, can be of the same type or different types.
[0440] In this invention, if the active material layer is formed from the electrode composition of this invention, an all-solid-state secondary battery with low resistance and excellent cycle characteristics can be realized.
[0441] (Current collector)
[0442] The positive current collector 5 and the negative current collector 1 are as described above.
[0443] In the all-solid-state secondary battery 10 described above, when it has a constituent layer other than the constituent layer formed by the electrode composition of the present invention, a layer formed by a known constituent layer forming material can also be applied.
[0444] Furthermore, each layer can be a single layer or multiple layers.
[0445] [Manufacturing of all-solid-state rechargeable batteries]
[0446] All-solid-state secondary batteries can be manufactured using conventional methods. Specifically, all-solid-state secondary batteries can be manufactured by forming at least one active material layer using the electrode composition of the present invention, and forming a solid electrolyte layer, another suitable active material layer, or an electrode using known materials.
[0447] Specifically, the all-solid-state secondary battery of the present invention can be manufactured by a method comprising the steps of appropriately coating the electrode composition of the present invention onto the surface of a substrate (e.g., a metal foil serving as a current collector) and drying it to form a coating film (film forming method of the present invention for manufacturing electrode sheets for all-solid-state secondary batteries).
[0448] For example, a positive electrode active material layer is formed by coating an electrode composition containing a positive electrode active material as a positive electrode material (positive electrode composition) onto a metal foil serving as the positive electrode current collector to create a positive electrode sheet for an all-solid-state secondary battery. Next, a composition containing an inorganic solid electrolyte for forming a solid electrolyte layer is coated onto this positive electrode active material layer to form a solid electrolyte layer. Furthermore, a negative electrode active material layer is formed by coating an electrode composition containing a negative electrode active material as a negative electrode material (negative electrode composition) onto the solid electrolyte layer. By overlapping a negative electrode current collector (metal foil) onto the negative electrode active material layer, an all-solid-state secondary battery with a structure in which the solid electrolyte layer is sandwiched between the positive and negative electrode active material layers can be obtained. It can also be encapsulated in a casing to form a desired all-solid-state secondary battery.
[0449] Furthermore, in contrast to the methods for forming each layer, it is also possible to manufacture an all-solid-state secondary battery by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on the negative electrode current collector and then overlapping the positive electrode current collector.
[0450] As another method, the following approach can be used: The positive electrode sheet for an all-solid-state secondary battery is manufactured as described above. Furthermore, an electrode composition containing a negative electrode active material, serving as a negative electrode material (negative electrode composition), is coated onto a metal foil serving as the negative electrode current collector to form a negative electrode active material layer, thereby manufacturing the negative electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed on the active material layer of any one of these sheets, as described above. Moreover, the positive electrode sheet for an all-solid-state secondary battery and another negative electrode sheet for an all-solid-state secondary battery are stacked on the solid electrolyte layer in such a manner that the solid electrolyte layer and the active material layer are in contact. In this way, an all-solid-state secondary battery can be manufactured.
[0451] Furthermore, as another method, the following can be cited: That is, to manufacture the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery as described above. In addition, a solid electrolyte sheet for an all-solid-state secondary battery, consisting of a solid electrolyte layer, is manufactured by coating a composition containing an inorganic solid electrolyte onto a substrate. Moreover, the solid electrolyte layer, which has been peeled off from the substrate, is stacked in a manner where the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery hold it in place. In this way, an all-solid-state secondary battery can be manufactured.
[0452] Furthermore, as described above, a positive electrode sheet or a negative electrode sheet for an all-solid-state secondary battery and a solid electrolyte sheet for an all-solid-state secondary battery are manufactured. Next, the positive electrode sheet or a negative electrode sheet and the solid electrolyte sheet for an all-solid-state secondary battery are overlapped while the positive electrode active material layer or a negative electrode active material layer is in contact with the solid electrolyte layer, and pressure is applied. This transfers the solid electrolyte layer onto the positive electrode sheet or the negative electrode sheet for an all-solid-state secondary battery. Then, the solid electrolyte layer obtained by peeling off the substrate of the solid electrolyte sheet for an all-solid-state secondary battery and the negative electrode sheet or the positive electrode sheet for an all-solid-state secondary battery (while the negative electrode active material layer or the positive electrode active material layer is in contact with the solid electrolyte layer) are overlapped and pressure is applied. In this way, an all-solid-state secondary battery can be manufactured. There are no particular limitations on the pressure application method and conditions in this method; the methods and conditions described in the pressure application process described later can be used.
[0453] The active material layer, for example, can also be used to form an electrode composition by pressure molding on a substrate or active material layer under pressure conditions described later, and a sheet molded body of a solid electrolyte or active material can also be used.
[0454] In the above manufacturing method, either the positive electrode composition or the negative electrode composition can use the electrode composition of the present invention, and both the positive electrode composition and the negative electrode composition can use the electrode composition of the present invention.
[0455] <Formation of each layer (film formation)>
[0456] There are no particular limitations on the coating method for each composition, and it can be appropriately selected. For example, wet coating methods such as coating (preferably wet coating), spraying, spin coating, dip coating, slot coating, strip coating, and bar coating can be mentioned. There are no particular limitations on the coating temperature, for example, a temperature range at the normal room temperature without heating (e.g., 15 to 30°C) can be mentioned.
[0457] It is preferable to perform a drying treatment (heat treatment) on the coated composition. The drying treatment can be performed after each coating of the composition or after multiple coatings. The drying temperature is not particularly limited as long as it is sufficient to remove the dispersion medium, and is appropriately set according to the boiling point of the dispersion medium, etc. For example, the lower limit of the drying temperature is preferably 30°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. The upper limit is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower. By heating within such a temperature range, the dispersion medium can be removed to obtain a solid state (coated dried layer). Furthermore, it is preferable that the temperature is not too high and the components of the all-solid-state secondary battery are not damaged. Thus, when the electrode composition of the present invention is coated and dried, deviations in the contact state can be suppressed and solid particles can be bonded together, and a coated dried layer with a flat surface can be formed.
[0458] After coating each composition, the layers are overlapped to form a solid-state secondary battery, or after fabrication of the all-solid-state secondary battery, each layer or the all-solid-state secondary battery is pressurized. Furthermore, pressurization is preferably performed while the layers are stacked. Examples of pressurization methods include hydraulic cylinder presses. There are no particular limitations on the pressurization pressure, but a range of 5 to 1500 MPa is generally preferred.
[0459] Furthermore, the coated compositions can be heated simultaneously with pressurization. There are no particular limitations on the heating temperature, which is generally in the range of 30 to 300°C. Stamping can also be performed at temperatures higher than the glass transition temperature of the inorganic solid electrolyte. Additionally, stamping can also be performed at temperatures higher than the glass transition temperature of the polymer constituting the polymer binder. However, the temperature is generally not higher than the melting point of the polymer.
[0460] Pressurization can be performed either with the solvent or dispersion medium pre-dried or with residual solvent or dispersion medium remaining.
[0461] Alternatively, the various compositions can be coated simultaneously, or the coating, drying, and stamping can be performed simultaneously and / or sequentially. They can be laminated by transfer printing after being coated onto their respective substrates.
[0462] There are no particular limitations on the atmosphere used in film-forming methods (coating, drying, pressurization (under heating)). It can be any environment, such as atmospheric pressure, dry air (dew point below -20°C), or inert gases (e.g., argon, helium, nitrogen).
[0463] The stamping time can be either a short period of high pressure (e.g., within a few hours) or a long period of medium pressure (more than one day). In cases other than electrode sheets for all-solid-state secondary batteries, such as in the case of all-solid-state secondary batteries, the constraint tools for all-solid-state secondary batteries (such as screw tightening pressure) can be used to continuously apply medium pressure. The stamping pressure can be uniform or varied relative to the pressure-bearing area, such as the sheet surface. The stamping pressure can be varied according to the area or film thickness of the pressure-bearing area. Furthermore, different pressures can be applied to the same area in stages. The stamped surface can be smooth or rough.
[0464] <Initialization>
[0465] All-solid-state secondary batteries manufactured in the manner described above are preferably initialized after manufacturing or before use. Initialization is not particularly limited; for example, initial charging and discharging can be performed under increased stamping pressure, followed by releasing the pressure until the normal operating pressure of the all-solid-state secondary battery is reached.
[0466] Applications of all-solid-state rechargeable batteries
[0467] The all-solid-state secondary battery of this invention is applicable to a wide variety of uses. There are no particular limitations on its application; for example, when incorporated into electronic devices, it can be used in laptops, pen-and-paper computers, mobile computers, e-book readers, mobile phones, cordless phones, pagers, handheld terminals, portable fax machines, portable copiers, portable printers, stereo headphones, camcorders, LCD TVs, handheld vacuum cleaners, portable CD players, mini disk drives, electric shavers, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, etc. As other civilian products, it can be used in automobiles (electric vehicles), electric vehicles, motors, lighting fixtures, toys, game consoles, load conditioners, clocks, flashlights, cameras, and medical devices (pacemakers, hearing aids, and shoulder massagers, etc.). Furthermore, it can be used in various military and aerospace applications. It can also be combined with solar cells.
[0468] Example
[0469] The present invention will now be described in further detail with reference to embodiments, but the invention is not limited thereto. In the following embodiments, unless otherwise specified, "parts" and "%" of composition refer to mass. In the present invention, "room temperature" refers to 25°C.
[0470] 1. Polymer Synthesis
[0471] Polymers B-1 to B-21, as shown in the following chemical formulas, are synthesized as follows, and adhesive solutions or dispersions containing each polymer B-1 to B-21 are prepared.
[0472] [Synthesis Example B-1] Synthesis of Polymer B-1 and Preparation of Adhesive Solution B-1
[0473] A monomer solution was prepared by adding 90 g of dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 10 g of 2-methoxyethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 3.6 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation) to a 100 mL volumetric flask and dissolving them in 36 g of butyl butyrate. 18 g of butyl butyrate was then added dropwise to a 300 mL three-necked flask, and the monomer solution was added dropwise over 2 hours at 80 °C with stirring. After the addition was complete, the temperature was raised to 90 °C and stirred for 2 hours to synthesize polymer B-1 (acrylic polymer). The obtained solution was then precipitated in methanol and dissolved in xylene.
[0474] Thus, an acrylic polymer B-1 with a mass-average molecular weight of 400,000 was synthesized, thereby preparing an adhesive solution B-1 (concentration 10% by mass) composed of this polymer.
[0475] [Synthesis Example B-2] Synthesis of Polymer B-2 and Preparation of Adhesive Solution B-2
[0476] In a nitrogen-purged and dried pressure vessel, 300 g of cyclohexane as solvent and 1.0 mL of sec-butyllithium (1.3 M, manufactured by FUJIFILM Wako Pure Chemical Corporation) as polymerization initiator were added. The mixture was heated to 50 °C, and 15.5 g of styrene was added, followed by polymerization for 2 hours. Then, 24.0 g of 1,3-butadiene and 45.0 g of ethylene were added, and polymerization continued for 3 hours. Finally, 15.5 g of styrene was added, and polymerization continued for 2 hours. The resulting solution was then precipitated in methanol, and the solid was dried. 100 parts by weight of the resulting polymer were added to 3 parts by weight of 2,6-di-tert-butyl-p-cresol, and the reaction was carried out at 180 °C for 5 hours. The resulting solution was then precipitated in acetonitrile, and the solid was dried at 80 °C to obtain the polymer (dry solid). Subsequently, in a pressure vessel, the obtained polymer was completely dissolved in 400 parts by mass of cyclohexane. Then, 5% by mass palladium on carbon (palladium loading: 5% by mass) was added to the polymer as a hydrogenation catalyst, and the reaction was carried out for 10 hours under hydrogen pressure of 2 MPa and 150°C. After cooling and depressurization, the palladium on carbon was removed by filtration, the filtrate was concentrated, and further vacuum dried to obtain hydrocarbon polymer B-2.
[0477] Then, it was dissolved in xylene to prepare adhesive solution B-2 (concentration 10% by mass).
[0478] [Synthesis Example B-3] Synthesis of Polymer B-3 and Preparation of Adhesive Solution B-3
[0479] 100 parts by mass of ion-exchanged water, 64 parts by mass of vinylidene fluoride, 17 parts by mass of hexafluoropropylene, and 19 parts by mass of tetrafluoroethylene were added to an autoclave. Then, 1 part by mass of the polymerization initiator PEROYL IPP (trade name, chemical name: diisopropyl peroxide, manufactured by NOF CORPORATION) was added, and the mixture was stirred at 40°C for 24 hours. After stirring, the precipitate was filtered and dried at 100°C for 10 hours. 150 parts by mass of toluene or N-methylpyrrolidone were added to 10 parts by mass of the obtained polymer and dissolved.
[0480] Thus, a random copolymer fluoropolymer B-3 was synthesized, thereby preparing an adhesive solution B-3 (concentration 10% by mass) composed of this polymer.
[0481] [Synthesis Example B-4] Synthesis of Polymer B-4 and Preparation of Adhesive Solution B-4
[0482] A monomer solution was prepared by adding 9.9 g of methyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 90 g of dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.07 g of maleic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.03 g of monomethyl maleate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 3.6 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako PureChemical Corporation) to a 100 mL volumetric flask and dissolving it in 36 g of butyl butyrate. 18 g of butyl butyrate was then added dropwise to a 300 mL three-necked flask, and the monomer solution was added dropwise over 2 hours with stirring at 80 °C. After the addition was complete, the temperature was raised to 90 °C and stirred for 2 hours to synthesize polymer B-4 (acrylic polymer). The obtained solution was then precipitated in acetonitrile and dissolved in xylene.
[0483] Thus, an acrylic polymer B-4 with a mass-average molecular weight of 400,000 was synthesized, thereby preparing an adhesive solution B-4 (concentration 10% by mass) composed of this polymer.
[0484] [Synthetic Examples B-5 to 9, 11, 12, 14 and 19]
[0485] Synthesis of polymers B-5 to 9, 11, 12, 14 and 19 and preparation of adhesive solutions B-5 to 9, 11, 12, 14 and 19
[0486] In Synthesis Example B-4, compounds containing each constituent component were used to achieve the structure and composition (content of constituent components) shown in the following structural formula. Otherwise, acrylic polymers B-5 to 9, 11, 12, 14 and 19 were synthesized in the same manner as in Synthesis Example B-4, and adhesive solutions B-5 to 9, 11, 12, 14 and 19 (concentration 10% by mass) composed of each polymer were prepared.
[0487] [Synthesis Example B-10] Synthesis of Polymer B-10 and Preparation of Adhesive Dispersion B-10
[0488] A monomer solution was prepared by adding 200g of n-butyl acrylate, 200g of methacrylic acid, 16.5g of 3-mercaptopropionic acid, and 7.8g of polymerization initiator V-601 (manufactured by FUJIFILM Wako Pure Chemical Corporation) to a 1L graduated cylinder and stirring until homogeneous. 465.5g of toluene (manufactured by FUJIFILM Wako Pure Chemical Corporation) was added dropwise to a 2L three-necked flask and stirred at 80°C for 2 hours. After the addition was complete, the mixture was stirred at 80°C for 2 hours, then the temperature was raised to 90°C and stirred for another 2 hours. Next, 275 mg of 2,2,6,6-tetramethylpiperidin-1-oxy (manufactured by FUJIFILM Wako Pure Chemical Corporation), 27.5 g of glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 5.5 g of tetrabutylammonium bromide (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and the mixture was stirred at 120°C for 3 hours. After the solution was allowed to stand at room temperature, it was poured into 1800 g of methanol, and the supernatant was removed. Butyl butyrate was added to the solution, and methanol was removed by distillation under reduced pressure to obtain a butyl butyrate solution of the macromonomer M-1 (number average molecular weight 12,000). The solids concentration was 49% by mass.
[0489] A monomer solution was prepared by adding 28.8 g of methoxyethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 1.40 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation) to a 100 mL graduated cylinder and dissolving them in 28.8 g of butyl butyrate.
[0490] 19.6 g of macromonomer M-1 solution and 36.0 g of butyl butyrate were added to a 300 mL three-necked flask. The monomer solution was added dropwise over 2 hours while stirring at 80 °C. After the addition was complete, the temperature was raised to 90 °C and stirred for another 2 hours.
[0491] Subsequently, it was mixed with xylene and dispersed into particles to prepare a binder dispersion B-10 of propylene polymer B-10 (concentration 10% by mass). The average particle size in the dispersion of propylene polymer B-10 was 200 nm.
[0492] [Synthesis Example B-13] Synthesis of Polymer B-13 and Preparation of Adhesive Solution B-13
[0493] In Synthesis Example B-1, 99.7 g of dodecyl acrylate and 0.3 g of methacrylic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were used instead of 90 g of dodecyl acrylate and 2-methoxyethyl acrylate. Otherwise, acrylic polymer B-13 was synthesized in the same manner as in Synthesis Example B-1, thereby preparing adhesive solution B-13 (concentration 10% by mass).
[0494] [Synthesis Example B-15] Synthesis of Polymer B-15 and Preparation of Adhesive Solution B-15
[0495] In Synthesis Example B-1, 0.5 g of AS-6 (trade name, styrene macromonomer, number average molecular weight 6000, manufactured by TOAGOSEI CO.,LTD.) and 9.5 g of 2-methoxyethyl acrylate were used. Otherwise, acrylic polymer B-15 was synthesized in the same manner as in Synthesis Example B-1, thereby preparing an adhesive solution B-15 (concentration 10% by mass) composed of the polymer.
[0496] [Synthesis Example B-16] Synthesis of Polymer B-16 and Preparation of Adhesive Solution B-16
[0497] A monomer solution was prepared by adding 2.7 g of 2-hydroxyethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.1 g of monomethyl maleate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.2 g of maleic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.), 77 g of dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1.8 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako PureChemical Corporation) to a 100 mL volumetric flask and dissolving them in 36 g of butyl butyrate. The monomer solution was then added dropwise to a 300 mL three-necked flask with stirring at 80 °C for 2 hours. After the addition was complete, the temperature was raised to 90 °C and stirred for 2 hours. Next, 20g of methyl methacrylate and 1.8g of polymerization initiator V-6011 were added, and the mixture was stirred at 90°C for 2 hours. The resulting solution was then precipitated in acetonitrile and dissolved in xylene.
[0498] Thus, propylene polymer B-16, which is an ABA-type block polymer, was synthesized, thereby preparing an adhesive solution B-16 (concentration 10% by mass) composed of this polymer.
[0499] [Synthesis Example B-17] Synthesis of Polymer B-17 and Preparation of Adhesive Solution B-17
[0500] In Synthesis Example B-1, 97 g of dodecyl acrylate, 2.7 g of 2-hydroxyethyl methacrylate, 0.1 g of monomethyl maleate, and 0.2 g of maleic anhydride were used. Otherwise, acrylic polymer B-17 was synthesized in the same manner as in Synthesis Example B-1, thereby preparing an adhesive solution B-17 (concentration 10% by mass) composed of the polymer.
[0501] [Synthesis Example B-18] Synthesis of Polymer B-18 and Preparation of Adhesive Solution B-18
[0502] In the synthesis of macromonomer M-1 in Synthesis Example B-10, 420 g of dodecyl acrylate, 40 g of maleic anhydride, and 40 g of monomethyl maleate were used instead of n-butyl acrylate and methacrylic acid. Otherwise, macromonomer M-2 (number average molecular weight 15,000) was synthesized in the same manner as in the synthesis example of macromonomer M-1.
[0503] In Synthesis Example B-10, 72g of dodecyl acrylate and 3g of 2-hydroxyethyl methacrylate were used instead of methoxyethyl methacrylate, and 25g of macromonomer M-2 (solid content) was used instead of macromonomer M-1. Otherwise, acrylic polymer B-18 was synthesized in the same manner as in Synthesis Example B-10, thereby preparing an adhesive solution B-18 (concentration 10% by mass) composed of the polymer.
[0504] [Synthesis Example B-20] Synthesis of Polymer B-20 and Preparation of Adhesive Solution B-20
[0505] In Synthesis Example B-1, 90 g of dodecyl acrylate, 9.91 g of methyl methacrylate, and 0.09 g of monomethyl maleate were used. Otherwise, acrylic polymer B-20 was synthesized in the same manner as in Synthesis Example B-1, thereby preparing an adhesive solution B-20 (concentration 10% by mass) composed of the polymer.
[0506] [Synthesis Example B-21] Synthesis of Polymer B-21 and Preparation of Adhesive Solution B-21
[0507] In Synthesis Example B-1, 84.7 g of dodecyl acrylate, 15 g of styrene, and 0.3 g of monomethyl maleate were used. Otherwise, acrylic polymer B-21 was synthesized in the same manner as in Synthesis Example B-1, thereby preparing an adhesive solution B-21 (concentration 10% by mass) composed of the polymer.
[0508] The synthesized polymers are shown below. Polymer B-16 is a block polymer and is labeled in the same manner as described above. The numbers listed in the lower right corner of each component indicate the content (mass %). In polymers B-4, etc., x represents the value that satisfies the "content of functional group (a)" listed in Table 1, and polymer B-16 represents the ratio of the contents of the two end blocks. In the following structural formula, Me represents methyl.
[0509] [Chemical Formula 6]
[0510]
[0511] [Chemical Formula 7]
[0512]
[0513] [Chemical Formula 8]
[0514]
[0515] The mass-average molecular weight (Mw) and SP value of each synthesized polymer were calculated based on the above method. These results are shown in Table 1. The unit of SP value is MPa. 1 / 2 However, the unit is omitted in the table.
[0516] Furthermore, in Table 1, the content of each functional group in "Content (mass%)" is expressed as the content in polymer (b) containing the functional group. In polymer B-18, one functional group (a) has both a carboxyl group and a carboxylic anhydride group; therefore, the content of functional group (a) is set as the content in polymer (b) containing the aforementioned functional group.
[0517] In Table 1, the "x" in the above chemical formula has been added. However, since polymer B-16 is unknown, it is indicated by "-" in this column.
[0518] [Table 1]
[0519]
[0520] 2. Synthesis of sulfide-based inorganic solid electrolytes
[0521] [Synthetic Example S]
[0522] The sulfide-based inorganic solid electrolyte was synthesized with reference to non-patent literature, T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.
[0523] Specifically, 2.42 g of lithium sulfide (Li₂S, manufactured by Aldrich, Inc., purity > 99.98%) and 3.90 g of phosphorus pentasulfide (P₂S₅, manufactured by Aldrich, Inc., purity > 99%) were weighed out in a glove box under an argon atmosphere (dew point -70°C) and added to an agate mortar. The mixture was then mixed for 5 minutes using an agate pestle. The molar ratio of Li₂S to P₂S₅ was set as Li₂S:P₂S₅ = 75:25.
[0524] Next, 66g of 5mm diameter zirconia beads were added to a 45mL zirconia container (manufactured by Fritsch Co., Ltd.), along with the total amount of the aforementioned mixture of lithium sulfide and phosphorus pentasulfide. The container was then completely sealed under an argon atmosphere. The container was placed in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.) and mechanically ground (micronized) at 25°C and 510 rpm for 24 hours, yielding 6.20g of a yellow powder sulfide-based inorganic solid electrolyte (Li-PS glass, hereinafter, sometimes labeled LPS).
[0525] In this way, the inorganic solid electrolyte LPS with a particle size of 5 μm was synthesized.
[0526] [Example 1]
[0527] <Preparation of the positive electrode composition (slurry)>
[0528] 2.8 g of the inorganic solid electrolyte (SE) and xylene with the following isomer mixing ratio as a dispersion medium (D) were added to a container in a rotation-revolution mixer (ARE-310, manufactured by THINKY CORPORATION) to make the content of dispersion medium (D) in the positive electrode composition reach 50% by mass. The container was then placed in the ARE-310 rotation-revolution mixer (trade name) and mixed for 2 minutes at 25°C and 2000 rpm. Afterwards, LiNi as the positive electrode active material (AC) was added to the container in the proportions shown in Table 2-1.1 / 3 Co 1 / 3 Mn 1 / 3 O2 (manufactured by NMC, Sigma-Aldrich, Inc.), acetylene black (AB) as a conductive additive (CA), and the binder solution (B) or binder dispersion shown in Table 2-1 below (labeled as "binder solution or dispersion" in Table 2-1) were mixed for 2 minutes at 25°C and 2000 rpm in a rotary-revolutionary mixer to prepare positive electrode compositions (slurries) P-1 to P-24. Note that the binder solution or dispersion content refers to the content of the solid components.
[0529] <Preparation of the negative electrode composition (slurry)>
[0530] 2.8 g of the inorganic solid electrolyte (SE) shown in Table 3-1, 0.06 g (solid mass) of the binder solution (B) or dispersion shown in Table 3-1 (labeled as "binder solution or dispersion" in Table 3-1), and xylene as the dispersion medium (D) with the following isomer mixing ratio were added to a container in a rotation-revolution mixer (ARE-310) to make the content of dispersion medium (D) in the negative electrode composition 50% by mass. The container was then placed in a THINKY CORPORATION rotation-revolution mixer ARE-310 (trade name) and mixed for 2 minutes at 25°C and 2000 rpm. Subsequently, 3.11 g of silicon (Si, manufactured by Aldrich) as the negative electrode active material (AC) and 0.25 g of acetylene black (AB) as the conductive additive (CA) were added and placed in the same rotation-revolution mixer ARE-310 (trade name) and mixed for 2 minutes at 25°C and 2000 rpm to prepare negative electrode compositions (slurries) N-1 to N-24.
[0531] In addition, the negative electrode composition (slurry) N-19 uses 2.86g of inorganic solid electrolyte (SE) and does not use binder solution (B).
[0532] The adsorption rate of the polymer binder (B) used to prepare the electrode composition to the conductive additive (CA) [A] CA ] and the adsorption rate of inorganic solid electrolytes (SE) [A SE The values measured by the above methods are shown in Tables 2-2 and 3-2, respectively.
[0533] Furthermore, the average particle size of the conductive additive (CA) was determined as follows (condition (4A)) when the polymer binder (B), dispersion medium (D), and conductive additive (CA) were mixed in the same mass ratio as the electrode composition. Specifically, the polymer binder (B), dispersion medium (D), and conductive additive (CA) used to prepare each electrode composition were mixed in the mass ratios shown in Table 2-1 or Table 3-1 to prepare a dispersion for measurement. The preparation conditions were: using a mixing rotor (manufactured by AS ONE Corporation), at room temperature, a rotation speed of 50 rpm, and a stirring time of 3 hours. The obtained dispersion for measurement was analyzed using a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) at 25°C, with 50 data reads performed using a quartz cuvette for measurement, and the obtained volume average particle size was calculated. Other detailed conditions were referred to JIS Z 8828:2013 "Particle size analysis - dynamic light scattering method" as needed. Five samples were prepared for each grade for testing, and the average value was set as the average particle size of the conductive additive (CA) (condition (4A)). The results are shown in the “Average Particle Size under Condition (4A)” column of Tables 2-2 and 3-2.
[0534] In addition, the SP value of the dispersion medium and the difference ΔSP (absolute value) between the SP value of the dispersion medium (D) and the SP value of the polymer (b) forming the polymer binder (B) are calculated and shown in the respective tables.
[0535] Furthermore, regarding the combination of polymer binder (B) and dispersion medium (D) used to prepare the electrode compositions described in Tables 2-1 and 3-1 below, the solubility of the dispersion medium (D) for the synthesized polymers B-1 to B-9 and B-11 to B-21, determined by the aforementioned transmittance measurement, was 10% by mass or more, and was shown as "soluble" in the "Solubility" column of Tables 2-2 and 3-2. On the other hand, the solubility of polymer B-10 was less than 10% by mass, and was shown as "particulate" in the "Solubility" column of Tables 2-2 and 3-2.
[0536] In addition, the units for content (mass%), SP values, and the difference in SP values ΔSP (MPa) are omitted in each table. 1 / 2 ), adsorption rate (%) and average particle size (μm).
[0537] [Table 2-1]
[0538]
[0539] [Table 2-2]
[0540]
[0541] [Table 3-1]
[0542]
[0543] [Table 3-2]
[0544]
[0545] <Abbreviation for table>
[0546] NMC: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (manufactured by Aldrich, particle size 5μm)
[0547] LPS: LPS synthesized in synthesis example S
[0548] AB: Acetylene Black (manufactured by Denka Company Limited, particle size 35nm, bulk density 0.04g / ml)
[0549] AB2: Acetylene Black (manufactured by Denka Company Limited, particle size 48nm, bulk density 0.15g / ml)
[0550] CB: Carbon black SUPER-P Li (manufactured by IMERYS, particle size 40nm)
[0551] Si: Silicon (manufactured by Kojundo Chemical Lab.Co.,Ltd., particle size 5μm)
[0552] A mixture of xylene isomers with a molar ratio of ortho-isomer: para-isomer: meta-isomer = 1:5:2.
[0553] <Fabrication of Positive Electrode Sheets for All-Solid-State Secondary Batteries>
[0554] Using a baking-type applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), the above-obtained positive electrode compositions P-1 to P-24 were coated onto 20 μm thick aluminum foil at room temperature. The positive electrode compositions were then heated at 110°C for 1 hour and dried (dispersion medium removed). Subsequently, using a hot press, the dried positive electrode compositions were pressurized at 25°C (10 MPa, 1 minute) to produce positive electrode sheets P-1 to P-24 for all-solid-state secondary batteries, each with a 100 μm thick positive electrode active material layer.
[0555] <Fabrication of negative electrode sheets for all-solid-state secondary batteries>
[0556] Using a baking applicator (trade name: SA-201), the aforementioned negative electrode compositions N-1 to N-24 were coated onto a 20 μm thick copper foil at room temperature. The foil was heated at 110°C for 1 hour, and then dried using a vacuum dryer AVO-200NS (trade name, manufactured by AS ONE Corporation) at 110°C for 2 hours to remove the dispersion medium. Subsequently, the dried negative electrode compositions were pressurized at 25°C (10 MPa, 1 minute) using a hot press to fabricate all-solid-state secondary battery negative electrode sheets N-1 to N-24, each with a 70 μm thick negative electrode active material layer.
[0557] The compositions and sheets manufactured were evaluated as follows, and the results are shown in Tables 4-1 and 4-2 (collectively referred to as Table 4).
[0558] <Evaluation 1: Dispersion Stability>
[0559] Each prepared composition (slurry) was placed into a glass test tube with a diameter of 10 mm and a height of 4 cm until the height reached 4 cm, and allowed to stand at 25°C for 24 hours. The reduction rate of solid content in the top 25% (height) of the composition before and after standing was calculated using the following formula. Based on whether this solid content reduction rate was included in any of the following evaluation criteria, the ease with which solid particles aggregated or precipitated over time was evaluated as the composition's storage stability (dispersion stability). In this test, the smaller the above solid content reduction rate, the better the dispersion stability; an evaluation criterion of "F" or above is considered acceptable.
[0560] Solid content reduction rate (%) = [(Solid content concentration of the top 25% before settling - Solid content concentration of the top 25% after settling) / Solid content concentration of the top 25% before settling] × 100
[0561] -Evaluation Criteria-
[0562] A: Solid content reduction rate < 0.5%
[0563] B: 0.5% ≤ Solid content reduction rate < 2%
[0564] C: 2% ≤ Solid content reduction rate < 5%
[0565] D: 5% ≤ Solid content reduction rate < 10%
[0566] E: 10% ≤ Solid content reduction rate < 15%
[0567] F: 15% ≤ Solid content reduction rate < 20%
[0568] G: 20% ≤ reduction rate of solid content
[0569] <Evaluation 2: Upper Limit Concentration of Pulping>
[0570] In the preparation of the above compositions (slurries), test compositions with a solids concentration of 76% by mass were prepared by adjusting the amount of dispersion medium. The prepared test compositions with a solids concentration of 76% by mass were placed in a container (a cylindrical container (5.0 cm in diameter, 7.0 cm in height) for a rotary mixer (trade name: ARE-310, manufactured by THINKYCORPORATION)) placed on a table until the volume reached approximately 1.0 cm. The container was then tilted 60 degrees from this position (relative to the vertical direction) to confirm whether it had the fluidity to the extent that it would sag (change) under its own weight within 10 seconds. If it did not sag (remain stationary) under its own weight and did not have fluidity, the above dispersion medium was added to reduce the solids concentration of the test compositions by 1% by mass. After dispersion at 2,000 rpm for 1 minute in the rotary mixer, the fluidity was checked again in the same manner as with the test compositions with a solids concentration of 76% by mass. The operation was repeated by decreasing the concentration of each solid component by 1% by mass, and the maximum concentration of solid components with flowability was taken as the upper limit of slurry preparation. The maximum concentration of thick slurry that could be prepared was evaluated. This experiment was conducted at 25°C.
[0571] When the concentration of solid components is increased to a level exceeding the upper limit of the slurry concentration, it becomes difficult to use the composition in the coating process. Therefore, the upper limit of the slurry concentration becomes an indicator of the upper limit of the solid component concentration of the composition that can be used in the coating process, and a higher level is preferred.
[0572] In Table 4 below, the upper limit concentration of slurry is expressed in mass%, but is omitted.
[0573] <Evaluation 3: Average particle size of conductive additives in the active material layer>
[0574] The average particle size of the conductive additives in the active material layer of the positive and negative electrode sheets for all-solid-state secondary batteries was measured as shown below, and the results are presented in Table 4. In Table 4, the unit of average particle size is "μm", but is omitted.
[0575] That is, the active material layer, which is prepared by cutting along the vertical direction, is observed using a scanning electron microscope (SEM) at a magnification of 5,000x to obtain SEM images. Conductive additives (single particles or aggregates) in 0.1 mm × 0.05 mm regions are randomly selected from 50 of these SEM images, and the area equivalent diameter of each conductive additive is calculated. The arithmetic mean of these is taken as the average particle size of the conductive additive (CA) present in the active material layer.
[0576] The boundaries of conductive additives (CA) in SEM images can be determined by binarization. Furthermore, when conductive additives (CA) form aggregates, the aggregates are treated as a single particle.
[0577] <Evaluation 4: Electron conductivity of the active material layer>
[0578] The electronic conductivity of the active material layer in the fabricated positive and negative electrodes for all-solid-state secondary batteries was measured as shown below, and the results are presented in Table 4. In Table 4, the unit of electronic conductivity is mS / cm, but is omitted.
[0579] Specifically, the electrode sheet for the all-solid-state secondary battery is stamped into a disc shape with a diameter of 10 mm and placed inside a PET cylinder with an inner diameter of 10 mm. A 10 mm SUS rod is inserted into the cylinder through both ends, and a pressure of 350 MPa is applied to the current collector side and active material layer side of the electrode sheet using the SUS rod. The cylinder is then fixed under a pressure of 50 MPa. Constant voltage measurement is performed using an impedance analyzer (VMP-300, manufactured by TOYO Corporation), and the current value I (mA) is read when the applied voltage V = 5.0 mV. The electronic conductivity σ is calculated using the following formula. e (mS / cm). Additionally, the thickness of the active material layer is set to D (μm). Furthermore, the thickness D of the positive electrode active material layer is 90 μm, and the thickness D of the negative electrode active material layer is 65 μm.
[0580] σ e (mS / cm)=I / V / 0.0785×D
[0581] [Table 4-1]
[0582]
[0583] [Table 4-2]
[0584]
[0585] <Manufacturing of All-Solid-State Secondary Batteries>
[0586] An all-solid-state secondary battery was manufactured by using the positive electrode sheet, the solid electrolyte sheet, and the negative electrode sheet for an all-solid-state secondary battery in the combination of the constituent layers shown in Tables 5-1 and 5-2 (collectively referred to as Table 5).
[0587] (Preparation of compositions (slurries) containing inorganic solid electrolytes)
[0588] In a container of a rotation-revolution mixer (ARE-310, manufactured by THINKY CORPORATION), 2.8 g of LPS synthesized in the above-described synthetic example S, 0.08 g of B-1 (solid component mass) as a polymer binder, and butyl butyrate as the dispersion medium were added to bring the content of the dispersion medium in the composition to 50% by mass. The container was then placed in the rotation-revolution mixer ARE-310 (trade name). Mixing was performed at 25°C and 2000 rpm for 5 minutes to prepare a composition (slurry) S-1 containing an inorganic solid electrolyte.
[0589] The composition of each component contains 97.2% LPS and 2.8% LPS per 100% by weight of solid components.
[0590] (Fabrication of solid electrolyte sheets for all-solid-state secondary batteries)
[0591] Using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), the aforementioned compositions S-1 containing inorganic solid electrolytes were coated onto aluminum foil with a thickness of 20 μm. The foil was then heated at 110°C for 2 hours and dried (to remove the dispersion medium) to produce solid electrolyte sheets S-1 for all-solid-state secondary batteries. The solid electrolyte layer had a film thickness of 50 μm.
[0592] (Manufacturing of all-solid-state secondary batteries)
[0593] The positive electrode sheet for the all-solid-state secondary battery shown in the "Positive Electrode No." column of Table 5 is stamped into a disc shape with a diameter of 10 mm and placed inside a PET cylinder with an inner diameter of 10 mm. Inside the cylinder, a solid electrolyte sheet S-1 for the all-solid-state secondary battery is also stamped into a disc shape with a diameter of 10 mm on the positive electrode active material layer side and placed inside the cylinder. 10 mm SUS rods are inserted from both ends of the cylinder (the positive electrode active material layer of the positive electrode sheet for the all-solid-state secondary battery is in contact with the solid electrolyte layer of the solid electrolyte sheet S-1). A pressure of 350 MPa is applied to the current collector side of the positive electrode sheet for the all-solid-state secondary battery and the aluminum foil side of the solid electrolyte sheet for the all-solid-state secondary battery through the SUS rods. The SUS rod on the solid electrolyte sheet side of the all-solid-state secondary battery was temporarily removed, and the aluminum foil of the solid electrolyte sheet was gently peeled off. Then, the all-solid-state secondary battery negative electrode sheet shown in the "Negative Electrode No." column of Table 5 was stamped into a disc shape with a diameter of 10 mm and inserted into the solid electrolyte layer of the all-solid-state secondary battery solid electrolyte sheet inside the cylinder (the solid electrolyte layer of solid electrolyte sheet S-1 is in contact with the negative electrode active material layer of the all-solid-state secondary battery negative electrode sheet). The removed SUS rod was reinserted into the cylinder and fixed under a pressure of 50 MPa. Thus, all-solid-state secondary batteries No. C-1 to C-48 with a stacked structure of aluminum foil (thickness 20 μm) - positive electrode active material layer (thickness 90 μm) - solid electrolyte layer (thickness 45 μm) - negative electrode active material layer (thickness 65 μm) - copper foil (thickness 20 μm) were obtained.
[0594] <Evaluation 5: Cyclic Characteristics (Discharge Capacity Retention) Test>
[0595] For each of the manufactured all-solid-state secondary batteries, the discharge capacity retention was measured using the TOSCAT-3000 charge-discharge evaluation device (trade name, manufactured by TOYO SYSTEM Co., Ltd.).
[0596] Specifically, each all-solid-state secondary battery was charged at 30°C until the current density reached 0.1 mA / cm². 2 And continue discharging until the battery voltage reaches 3.6V. Afterward, discharge until the current density reaches 0.1 mA / cm². 2 The battery voltage was maintained at 2.5V. One charge and one discharge cycle was considered one charge-discharge cycle, and this process was repeated for three cycles under the same conditions to initialize the battery. Afterwards, a current density of 3.0 mA / cm² was applied. 2 Charge until the battery voltage reaches 3.6V, at a current density of 3.0mA / cm². 2A high-speed charge-discharge cycle, consisting of discharging until the battery voltage reaches 2.5V, was defined as one cycle. This high-speed charge-discharge cycle was repeated 500 times. The discharge capacity of each all-solid-state secondary battery in the first high-speed charge-discharge cycle and the discharge capacity in the 500th high-speed charge-discharge cycle were measured using a charge-discharge evaluation device: TOSCAT-3000 (trade name). The discharge capacity retention rate was calculated using the following formula, and this discharge capacity retention rate was applied to the following evaluation criteria to evaluate the cycle characteristics of the all-solid-state secondary batteries. In this test, an evaluation criterion of "F" or higher was considered acceptable. The results are shown in Table 5.
[0597] In addition, the all-solid-state secondary batteries C-4 and C-23 were rated F, but their discharge capacity retention was 68%.
[0598] Discharge capacity retention rate (%)
[0599] = (Discharge capacity in the 500th cycle / Discharge capacity in the 1st cycle) × 100
[0600] In this experiment, the higher the evaluation standard, the better the battery performance (cycle characteristics), and the better the battery performance can be maintained even after repeated high-speed charge and discharge cycles (even after long-term use).
[0601] Furthermore, the discharge capacity of the all-solid-state secondary battery used for evaluation in this invention consistently showed values sufficient for its function as an all-solid-state secondary battery. Moreover, even without the aforementioned high-speed charge-discharge cycle, but under the same initialization conditions as described above, the all-solid-state secondary battery used for evaluation in this invention maintained excellent cycle characteristics.
[0602] -Evaluation Criteria-
[0603] A: 90% ≤ Discharge Capacity Maintenance Rate
[0604] B: 85% ≤ Discharge Capacity Retention < 90%
[0605] C: 80% ≤ Discharge capacity retention < 85%
[0606] D: 75% ≤ Discharge Capacity Retention < 80%
[0607] E: 70% ≤ Discharge capacity retention < 75%
[0608] F: 60% ≤ Discharge capacity retention < 70%
[0609] G: Discharge capacity retention rate < 60%
[0610] [Table 5-1]
[0611] C-1 P-1 S-1 N-1 G Comparative example C-2 P-2 S-1 N-1 G Comparative example C-3 P-3 S-1 N-1 G Comparative example C-4 P-4 S-1 N-1 F Example C-5 P-5 S-1 N-1 A Example C-6 P-6 S-1 N-1 B Example C-7 P-7 S-1 N-1 B Example C-8 P-8 S-1 N-1 C Example C-9 P-9 S-1 N-1 G Comparative example C-10 P-10 S-1 N-1 G Comparative example C-11 P-11 S-1 N-1 G Comparative example C-12 P-12 S-1 N-1 D Example C-13 P-13 S-1 N-1 G Comparative example C-14 P-14 S-1 N-1 G Comparative example C-15 P-15 S-1 N-1 A Example C-16 P-16 S-1 N-1 A Example C-17 P-17 S-1 N-1 B Example C-18 P-18 S-1 N-1 A Example C-19 P-19 S-1 N-1 G Comparative example C-39 P-20 S-1 N-1 E Example C-40 P-21 S-1 N-1 B Example C-41 P-22 S-1 N-1 A Example C-42 P-23 S-1 N-1 G Comparative example C-43 P-24 S-1 N-1 B Example
[0612] [Table 5-2]
[0613] C-20 P-1 S-1 N-1 G Comparative example C-21 P-1 S-1 N-2 G Comparative example C-22 P-1 S-1 N-3 G Comparative example C-23 P-1 S-1 N-4 F Example C-24 P-1 S-1 N-5 A Example C-25 P-1 S-1 N-6 B Example C-26 P-1 S-1 N-7 B Example C-27 P-1 S-1 N-8 C Example C-28 P-1 S-1 N-9 G Comparative example C-29 P-1 S-1 N-10 G Comparative example C-30 P-1 S-1 N-11 G Comparative example C-31 P-1 S-1 N-12 D Example C-32 P-1 S-1 N-13 G Comparative example C-33 P-1 S-1 N-14 G Comparative example C-34 P-1 S-1 N-15 A Example C-35 P-1 S-1 N-16 A Example C-36 P-1 S-1 N-17 B Example C-37 P-1 S-1 N-18 A Example C-38 P-1 S-1 N-19 G Comparative example C-44 P-1 S-1 N-20 E Example C-45 P-1 S-1 N-21 B Example C-46 P-1 S-1 N-22 A Example C-47 P-1 S-1 N-23 G Comparative example C-48 P-1 S-1 N-24 B Example
[0614] The following information can be gleaned from the results shown in Tables 4 and 5.
[0615] Electrode compositions P-19 and N-19 that do not contain the components specified in this invention, or electrode compositions that do not meet any of the conditions (1) to (4) specified in this invention, do not have sufficient storage stability. Therefore, in the active material layer formed by these compositions, the average particle size of the conductive additive is too large, or the electronic conductivity is insufficient, thus making it impossible to manufacture an all-solid-state secondary battery with excellent cycle characteristics.
[0616] In contrast, electrode compositions containing an inorganic solid electrolyte (SE), active material (AC), conductive additive (CA), dispersion medium (D), and polymer binder (B) and satisfying conditions (1) to (4) exhibit excellent dispersion stability even with high solid component concentrations. The active material layer of these electrode compositions contains conductive additives with small particle sizes and exhibits high electronic conductivity; all-solid-state secondary batteries with these active material layers can achieve low resistance and excellent cycle characteristics.
[0617] The invention has been described together with its embodiments, but unless otherwise specified, the invention is not limited in any detail of the description and should be interpreted broadly without departing from the spirit and scope of the invention as shown in the claims.
[0618] This application claims priority based on Japanese Patent Application 2021-113028, filed on July 7, 2021, the contents of which are incorporated herein by reference and are part of the description herein.
[0619] Symbol Explanation
[0620] 1-Negative current collector, 2-Negative active material layer, 3-Solid electrolyte layer, 4-Positive active material layer, 5-Positive current collector, 6-Working part, 10-All-solid-state secondary battery.
Claims
1. An electrode composition comprising: Inorganic solid electrolytes (SEs) that have conductivity with ions of metals belonging to Group 1 or Group 2 of the periodic table. Active substances (AC), Conductive additives (CA), Polymer adhesives (B) and dispersion medium (D), The polymer (b) constituting the polymer adhesive (B) is a (meth)acrylic acid polymer, wherein the (meth)acrylic acid polymer comprises a component containing a functional group and a substituent having 8 or more carbon atoms as a side chain component, wherein the component containing the functional group has at least one functional group selected from the following functional group group (a1). The dispersion medium (D) is an ester compound, ketone compound, ether compound, aromatic compound, or aliphatic compound. Furthermore, the electrode composition satisfies the following conditions (1) to (4). (1) The polymer binder (B) is dissolved in the dispersion medium (D). (2) The adsorption rate of the polymer adhesive (B) on the conductive additive (CA) in the dispersion medium (D) [A] CA [Above 0% and below 50%] (3) The polymer constituting the polymer adhesive (B) has a mass-average molecular weight of 6,000 or more. (4) The average particle size of the conductive additive (CA) present in the active material layer formed by the electrode composition is less than 1.0 μm; The total content of the functional group-containing components in the polymer (b) is 0.01 to 30% by mass, but when the functional group-containing components do not include components having a polymer chain having a functional group (a1) selected from the following functional group group (a1) as a substituent, the content is 0.01 to 8% by mass. The substituents having 8 or more carbon atoms constitute the side chain in polymer (b) at a content of 60–99.9% by mass. <Functional groups (a1)> Hydroxyl, carboxyl, ether, aryl, and carboxylic anhydride groups, The adsorption rate [A] CA The value is as follows: A 1% (w / w) polymer binder solution was prepared by dissolving polymer binder (B) in dispersion medium (D). The mass ratio of polymer binder (B) to conductive additive (CA) in this solution was 3:
1. The binder solution and conductive additive (CA) were placed in a 15 mL vial and stirred for 1 hour at 80 rpm using a mixing rotor at room temperature (25°C). After standing, the supernatant obtained through solid-liquid separation was filtered through a 1 μm filter. The filtrate was completely dried, and the mass of polymer binder (B) remaining in the filtrate, i.e., the mass of polymer binder (B) not adsorbed onto conductive additive (CA), was measured (W). PA The mass W PA and the mass W of the polymeric adhesive (B) contained in the adhesive solution used for the determination PB The adsorption rate of the polymer adhesive (B) for the conductive additive (CA) is calculated using the following formula. The average adsorption rate obtained by performing this operation twice is taken as the adsorption rate [A]. CA ](%), Adsorption rate [A] CA ](%)=[(W PB -W PA ) / W PB ]×100.
2. The electrode composition according to claim 1, wherein, The adsorption rate [A] CA It is between 5% and less than 30%.
3. The electrode composition according to claim 1 or 2, wherein, The adsorption rate of the polymer binder (B) on the inorganic solid electrolyte (SE) in the dispersion medium (D) [A] SE The percentage is below 45%. The adsorption rate [A] SE The value is as follows: A 1% (w / w) polymer binder solution was prepared by dissolving polymer binder (B) in dispersion medium (D). The mass ratio of polymer binder (B) to inorganic solid electrolyte (SE) in this solution was 42:
1. The binder solution and inorganic solid electrolyte (SE) were placed in a 15 mL vial and stirred for 1 hour at 80 rpm using a mixing rotor at room temperature (25°C). After standing, the supernatant obtained through solid-liquid separation was filtered through a 1 μm filter. The filtrate was completely dried, and the mass of polymer binder (B) remaining in the filtrate, i.e., the mass of polymer binder (B) not adsorbed onto the inorganic solid electrolyte (SE), was measured (W). A The mass W A and the mass W of the polymeric adhesive (B) contained in the adhesive solution used for the determination B The adsorption rate of the polymer binder (B) for the inorganic solid electrolyte (SE) is calculated using the following formula. The average adsorption rate obtained by performing this operation twice is taken as the adsorption rate [A]. SE ](%), Adsorption rate [A] SE ](%)=[(W B -W A ) / W B ]×100.
4. The electrode composition according to claim 1 or 2, wherein, The mass-average molecular weight is 10,000 to 700,000.
5. The electrode composition according to claim 1 or 2, wherein, The difference ΔSP between the SP value of the dispersion medium (D) and the SP value of the polymer (b) is 3.0 MPa. 1 / 2 the following.
6. The electrode composition according to claim 1 or 2, wherein, The inorganic solid electrolyte (SE) is a sulfide-based inorganic solid electrolyte.
7. An electrode sheet for an all-solid-state secondary battery, having an active material layer composed of the electrode composition according to any one of claims 1 to 6.
8. The electrode sheet for an all-solid-state secondary battery according to claim 7, wherein, The conductive additive (CA) in the active material layer has an average particle size of less than 0.5 μm.
9. The electrode sheet for an all-solid-state secondary battery according to claim 7, wherein, The electron conductivity of the active material layer is above 30 mS / cm.
10. An all-solid-state secondary battery, comprising sequentially a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein, At least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer composed of the electrode composition according to any one of claims 1 to 6.
11. A method for manufacturing an electrode sheet for an all-solid-state secondary battery, wherein, The electrode composition according to any one of claims 1 to 6 is used to form a film.
12. A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is manufactured by the manufacturing method described in claim 11.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A